Method for producing functional powder particles - Patents.com

The method addresses the limitations of conventional nano wire production by forming nano-scale structures on powder particles, enhancing surface area and properties, thus improving scalability and reducing costs.

JP7627043B2Active Publication Date: 2025-02-05KREMENAK NANOTECH INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021512792
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-09-07
Filing Date
2019-09-06
Publication Date
2025-02-05
Estimated Expiration
2039-09-06

AI Technical Summary

Technical Problem

Conventional methods for producing nano wires require high-temperature environments, are limited by the size of the processed substrate, and rely on expensive high-purity single crystal silicon wafers, restricting scalability and production throughput.

Method used

A method for forming structures on semiconductor or insulator powder particles, including processes to remove surface pollutants and oxides, and create specific nano-scale features such as pores, craters, and nano wires, using techniques like metal subsidy chemical etching and chemical etching to form homo- and hetero-functional structures.

Benefits of technology

Enables the production of nano-structured semiconductor powder particles with enhanced surface area and properties, allowing for increased reaction rates and scalability, while reducing costs and material requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627043000002
    Figure 0007627043000002
  • Figure 0007627043000003
    Figure 0007627043000003
  • Figure 0007627043000004
    Figure 0007627043000004
Patent Text Reader

Abstract

The present disclosure provides functionalized powder particles and methods for forming functionalized powder particles. The functionalization is achieved by the formation of primary and / or secondary structures on the powder particles. The functionalization can be controlled to produce a wide range of physical and / or chemical property variations. [Selection diagram] Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] cross reference This application claims the benefit of U.S. Provisional Patent Application No. 62 / 728,570, filed Sep. 7, 2018, the entirety of which is incorporated herein by reference. [Background technology]

[0002] Silicon is the second most abundant element in the earth's crust and is used commercially in construction, steel refining and the electronics industry. Pure silicon is an intrinsic semiconductor, but has too low an electrical conductivity to be used in electronics without doping it with small concentrations of other elements to increase its electrical conductivity. Specifically, single crystalline allotropes of silicon are used to produce silicon wafers used in the semiconductor industry. Recent research has focused on the formation of nanowires on silicon wafers for applications in photovoltaic devices and batteries. Methods for the synthesis of silicon nanowires include laser beam ablation, ion beam etching, chemical vapor deposition and liquid-vapor solid growth, and current research is focused on the controlled formation of nanowires along specific directions. Summary of the Invention

[0003] Conventional nanowire fabrication methods often require expensive high temperature and high vacuum environments, limiting the size, scalability and production throughput of processed substrates. Furthermore, conventional nanowire fabrication methods typically require high purity single crystal silicon wafers, which are expensive to produce and have limited potential applications due to their flat, fixed shape. There remains a great need for methods to produce structures, including nanostructures such as nanowires, on semiconductor (e.g., crystalline, polycrystalline, semi-crystalline, amorphous) powders, particles or grains. The present disclosure addresses such a need and provides related advantages.

[0004] In certain aspects, the present disclosure provides a method of forming structures on (e.g., powder) particles (e.g., particulates), the method including: (a) providing one or more (e.g., crystalline, polycrystalline, semi-crystalline, or amorphous) semiconductor or insulator powder particles; (b) (e.g., optionally) removing surface contaminants from the one or more powder particles; (c) (e.g., optionally) removing oxides from the one or more powder particles; (d) forming a first type of structures on the one or more powder particles, thereby forming one or more homofunctional powder particles; and (e) (e.g., optionally) forming a second type of structures on the one or more homofunctional powder particles, thereby forming one or more heterofunctional powder particles. In some embodiments, the first and / or second type structures are (e.g., optionally) selected from the group consisting of pores, depressions, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, grooves, fins, ridges, cliffs, pyramids, and inverted pyramids. In some embodiments, the (e.g., crystalline, polycrystalline, semicrystalline, or amorphous) powder particles are (e.g., crystalline, polycrystalline, semicrystalline, or amorphous) powder particles including Group IVA elements, Group IV-VI compounds, Group II-IVB compounds, Group I-VII compounds, Group II-VI compounds, Group III-V compounds, Group IV-IV compounds, transition metal oxides, and compounds of three or more elements. The powder particles may include one or more crystal grains, or the powder particles may consist of a single crystal grain.

[0005] In carrying out any of the subject methods, the method may include (b) removing surface contaminants from one or more powder particles. In some embodiments, the method may include (c) removing oxides from one or more powder particles. In some embodiments, the method may include (e) forming structures (e.g., of a second type) on one or more homofunctional powder particles, thereby forming one or more heterofunctional powder particles. The step of forming (d) may include forming structures (e.g., of a first type) on the surface or within the pores of the powder particles. The step of forming (e) may include forming structures (e.g., of a second type) on the surface or within the pores of the powder particles. At least one of the steps of forming (d) and (e) may include lithography. In some embodiments, each of the steps of forming (d) and (e) independently includes a process selected from the group consisting of metal-assisted chemical etching and chemical etching. At least one of the steps of forming (d) and (e) may include metal-assisted chemical etching, where the metal-assisted chemical etching includes depositing metal ions on the surface of the powder particles and etching the powder particles by exposing the metal ions to an etching solution. The metal ions may be selected from, for example, including but not limited to, precious and rare metals. In some embodiments, the etching solution is a plasma, a gas, or a solution. The etching solution may be a solution including an etching solution and an oxidizing agent. The first type of structure may be a submillistructure, such as a microstructure or a nanostructure. In some embodiments, the second type of structure is a submillistructure, such as a microstructure or a nanostructure. The methods described herein may further include exposing the one or more functional powder particles to a process selected from the group consisting of film coating, plating, chemical functionalization, doping, nanoparticle decoration, lithography, and combinations thereof.The first type structures and the second type structures may be selected from the group consisting of pores, pits, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, grooves, fins, ridges, cliffs, pyramids and inverted pyramids.

[0006] In some embodiments, the present disclosure provides a surface comprising one or more functional (e.g., crystalline, polycrystalline, semi-crystalline, or amorphous) (e.g., semiconducting or insulating) powder particles, where the powder particles (e.g., optionally) comprise one or more structures selected from pores, depressions, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, grooves, fins, ridges, cliffs, pyramids, and inverted pyramids, and the powder particles have a diameter of 0.01 to 10,000 microns. The powder particles (e.g., crystalline, polycrystalline, semi-crystalline, or amorphous) can be powder particles (e.g., crystalline, polycrystalline, semi-crystalline, or amorphous) of an element or compound selected from the group consisting of a Group IVA element, a Group IV-VI compound, a Group II-IVB compound, a Group I-VII compound, a Group II-VI compound, a Group III-V compound, a Group IV-IV compound, a transition metal oxide, and a compound of three or more elements. In some embodiments, the powder particles include one or more crystal grains, such as a single crystal grain. The powder particles can have a diameter of 0.1 μm to 1,000 μm. In some embodiments, the powder particles include two or more structures selected from the group consisting of a pore, a pit, a crater, a nanowire, a cone, a pinnacle, a pillar, a coral, a cord, a wall, a groove, a fin, a ridge, a cliff, a pyramid, and an inverted pyramid. One or more of the structures may be submillistructures, such as microstructures or nanostructures. In some embodiments, the average diameter of the smallest 30% of the powder particles is 200% smaller than the average diameter of the largest 10% of the powder particles. The surfaces described herein may further include a film that separates the powder particles from the atmosphere. The surface may be antireflective, reflective, absorptive, adsorptive, adhesive, refractive, abrasive, conductive, insulating, highly chemically reactive, chemically inert, luminescent, antibacterial, cytolytic, non-wetting, hydrophobic, hydrophilic, antifouling, anti-adhesive, anti-slip, antistatic, or a combination thereof.In some embodiments, the powder particles include one or more structures selected from the group consisting of pores, depressions, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, grooves, fins, ridges, cliffs, pyramids, and inverted pyramids. In some aspects, the present disclosure provides methods for transferring or replicating surface structures of an article, the methods including using functionalized (e.g., crystalline, polycrystalline, semi-crystalline, or amorphous semiconductor, or insulator) powder particles on one or more of the surfaces, referred to herein as a mold or mold.

[0007] In some embodiments, the present disclosure provides heterofunctional (e.g., crystalline, polycrystalline, or semicrystalline semiconductor or insulator) powder particles, where the powder particles include two or more types of submillistructures. In some embodiments, the present disclosure provides functional (e.g., crystalline, polycrystalline, semicrystalline, or amorphous semiconductor or insulator) powder particles, where the powder particles include submillistructures and further include film coating, plating, chemical functionalization, dopant, nanoparticle decoration, or surface termination. In some embodiments, the present disclosure provides homofunctional (e.g., crystalline, polycrystalline, semicrystalline, or amorphous semiconductor or insulator) powder particles, where the powder particles include structures selected from the group consisting of pores, craters, cones, pinnacles, pillars, corals, cords, walls, grooves, fins, ridges, cliffs, pyramids, and inverted pyramids. In some aspects, the present disclosure provides homofunctional (e.g., crystalline, polycrystalline, semi-crystalline, or amorphous semiconductor or insulator) powder particles, where the powder particles include structures selected from the group consisting of pores, depressions, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, grooves, fins, ridges, cliffs, pyramids, and inverted pyramids, where the powder particles are not elemental silicon particles. The powder particles described herein may have a diameter of 0.01 μm to 10,000 μm. In some embodiments, the diameter of the particles is 0.1 μm to 1,000 μm. The particles may be powder particles (e.g., crystalline, polycrystalline, semi-crystalline, or amorphous) of an element or compound selected from the group consisting of Group IVA elements, Group IV-VI compounds, Group II-IVB compounds, Group I-VII compounds, Group II-VI compounds, Group III-V compounds, Group IV-IV compounds, transition metal oxides, and compounds containing three or more elements. In some embodiments, the particles include one or more crystal grains. The particles may consist of a single crystal grain. The two or more types of submillistructures may be selected from the group consisting of pores, pits, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, grooves, fins, ridges, cliffs, pyramids, and inverted pyramids.In some embodiments, the two or more types of structures are selected from microstructures and nanostructures.

[0008] The particles described herein may reflect up to 10% of the total electromagnetic radiation (e.g., specular and / or diffuse) between 10 nm and 1 mm. In some embodiments, the particles may reflect up to 10% of the total electromagnetic radiation (e.g., specular and / or diffuse) between 10 nm and 400 nm. In some embodiments, the particles may reflect up to 10% of the total electromagnetic radiation (e.g., specular and / or diffuse) between 300 nm and 1,000 nm. In some embodiments, the particles may reflect up to 10% of the total electromagnetic radiation (e.g., specular and / or diffuse) between 700 nm and 1 mm. The particles may include two or more overlapping structures. The particles may be of regular or irregular shape. The particles described herein may further include film coating, plating, chemical functionalization, dopants, nanoparticle decoration, or surface termination. In some embodiments, the particles exhibit antimicrobial properties.

[0009] In some aspects, the disclosure provides methods of rupturing cell membranes, the methods comprising contacting cells with powder particles described herein (e.g., of a crystalline, polycrystalline, semi-crystalline, or amorphous semiconductor or insulator), where the powder particles physically or chemically interact with the cells, thereby rupturing the cells.

[0010] In some embodiments, the present disclosure provides a method of modifying the properties of a product, the method comprising incorporating one or more functional (e.g., crystalline, polycrystalline, semi-crystalline, or amorphous) (e.g., semiconductor or insulator) powder particles into the product, where the powder particles comprise one or more submillistructures, and the powder particles have a diameter of 0.01 μm to 10,000 μm. The (e.g., crystalline, polycrystalline, semi-crystalline, amorphous) powder particles may be (e.g., crystalline, polycrystalline, semi-crystalline, or amorphous) powder particles of an element or compound selected from the group consisting of Group IVA, Group IV-VI, Group II-IVB compounds, Group I-VII compounds, Group II-VI compounds, Group III-V compounds, Group IV-IV compounds, transition metal oxides, and compounds consisting of three or more elements. The powder particles may comprise one or more crystal grains. For example, the powder particles may consist of a single crystal grain. The powder particles may have a diameter of 0.1 to 1,000 μm. The powder particles may include two or more structures selected from the group consisting of pores, depressions, craters, nanowires, cones, pinnacles, pilasters, corals, cords, walls, grooves, fins, ridges, cliffs, pyramids, and inverted pyramids. In some embodiments, the one or more submillistructures are selected from the group consisting of pores, depressions, craters, nanowires, cones, pinnacles, pilasters, corals, cords, walls, grooves, fins, ridges, cliffs, pyramids, and inverted pyramids. The one or more structures may be selected from microstructures and nanostructures. In some examples, the product is selected from the group consisting of medical devices, cookware, appliances, countertops, vehicles, watercraft, and aircraft. The product may be selected from the group consisting of office consumables, office equipment, electronic equipment, containers, kitchen utensils, cooking utensils, household goods, textiles, hardware, consumer products, vehicles and marine, filters, pumps, aquatic equipment, surfaces, furniture, fixtures, equipment, building materials, armaments, tools, solar cells, currency, medical tools, medical devices, paper goods, manufacturing equipment, food processing equipment, and optical devices. In some embodiments, the product comprises rubber, plastic, metal, glass, or ceramic.The modifying step may include one or more of decreasing the absorbance of visible light, increasing the absorbance of visible light, decreasing the reflectance of light, increasing antimicrobial properties, increasing antifouling properties, increasing hydrophobicity, increasing hydrophilicity, increasing electrical conductivity, increasing electrical resistivity, increasing photoluminescence, increasing surface energy, decreasing surface energy, increasing coefficient of friction, and decreasing coefficient of friction of the product. The incorporating step may include coating the product with powder particles or embedding powder particles into the product. The methods described herein may further include exposing the product to a process selected from the group consisting of film coating, plating, chemical functionalization, doping, nanoparticle decoration, lithography, and combinations thereof.

[0011] In certain embodiments herein, methods are provided for (e.g., physically and / or non-chemically) lysing cells (or populations thereof), the methods comprising contacting the cells (or populations thereof) with functionalized (e.g., crystalline, polycrystalline, semi-crystalline, or amorphous) powder particles, where the powder particles comprise one or more submillistructures (e.g., as described in any suitable embodiment herein), and the powder particles have a diameter of 0.01 to 10,000 microns. In certain embodiments, the functionalized particles are comprised on the surface of the article. In other specific embodiments, the functionalized particles are not embedded in another material or surface, such as in a loose powder form. In some embodiments, all or a portion of the cells are physically lysed, where at least 30% of the cells are lysed (e.g., at least 50% of the cells are lysed). Any suitable particles provided herein are optionally utilized.

[0012] In certain embodiments herein, a low reflective surface (e.g., of an article of manufacture) is provided that comprises one or more functional crystalline, polycrystalline, semi-crystalline, or amorphous (e.g., semiconductor or insulator) powder particles (e.g., a surface that includes one or more of the particles configured on its surface and / or one or more particles embedded in its surface), where the powder particles (e.g., optionally) comprise one or more structures selected from pores, depressions, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, fins, ridges, cliffs, pyramids, and inverted pyramids, and where the powder particles have a diameter of 0.01 to 10,000 microns. In certain embodiments, the reflectance (e.g., of reflected and / or scattered light) is less than about 25% (e.g., less than about 15%, less than about 10%, etc.) than another comparable surface, and one or more powder particles are deficient (e.g., at a particular wavelength, such as IR, visible and / or UV wavelengths (e.g., at one or more wavelengths of light as described in the examples and figures disclosed herein). In further particular embodiments, the reflectance (e.g., of reflected and / or scattered light) of the surface is less than 5% (e.g., less than 4%, less than 3%, less than 2%, less than 1%, less than 0.5%, less than 0.2%, etc.) (e.g., at a particular wavelength, such as IR, visible and / or UV wavelengths). In certain embodiments, the surface is a (e.g., bulk) material in which the powder particles are incorporated and / or in which the material, and the material is silicon or silicon monoxide. In some embodiments, the powder particles are any of the particles of one of the preceding claims. Any suitable particles provided herein are optionally utilized.

[0013] In other embodiments provided herein are methods of modifying the light reflectance of an article, the methods comprising incorporating one or more functional crystalline, polycrystalline, semi-crystalline, or amorphous semiconductor or insulator powder particles into the article (e.g., a surface and / or its bulk material), where the powder particles comprise one or more submillistructures, and the powder particles have a diameter of 0.01 to 10,000 microns. In some embodiments, the crystalline, polycrystalline, semi-crystalline, or amorphous powder particles are crystalline, polycrystalline, semi-crystalline, or amorphous powder particles of an element or compound selected from Group IVA elements, Group IV-VI compounds, Group II-IVB compounds, Group I-VII compounds, Group II-VI compounds, Group III-V compounds, Group IV-IV compounds, transition metal oxides, and compounds comprising three or more elements. In certain embodiments, the one or more submillistructures are selected from pores, depressions, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, fins, ridges, cliffs, pyramids, and inverted pyramids. In some embodiments, the reflectance (e.g., of reflected and / or scattered light) is less than about 25% (e.g., less than about 15%, less than about 10%, etc.) than other comparable surfaces and is devoid of one or more powder particles (e.g., at a particular wavelength, such as IR, visible, and / or UV wavelengths). In certain embodiments, the reflectance (e.g., of reflected and / or scattered light) of the surface is less than 5% (e.g., less than 4%, less than 3%, less than 2%, less than 1%, less than 0.5%, less than 0.2%, etc.) (e.g., at a particular wavelength, such as IR, visible, and / or UV wavelengths). Any suitable particles provided herein are optionally utilized.

[0014] In some embodiments herein, a fade-resistant pigment (or a product including the pigment incorporated into or on a surface thereof) is provided, the pigment comprising functional crystalline, polycrystalline, semi-crystalline, amorphous (e.g., semiconducting or insulating) powder particles, wherein the powder particles (e.g., optionally) comprise one or more structures selected from pores, depressions, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, fins, ridges, cliffs, pyramids, and inverted pyramids, and the powder particles have a diameter of 0.01 to 10,000 microns. In certain embodiments, the powder particles are any of the particles of one of the preceding claims. Any suitable particles provided herein are optionally utilized.

[0015] In certain embodiments, provided herein is a method of forming a fade-resistant product, the method comprising incorporating into the product (e.g., its surface or the bulk of the material) one or more light-fading-resistant functional crystalline, polycrystalline, semi-crystalline, amorphous (e.g., semiconductor or insulator) powder particles, wherein the powder particles comprise one or more structures selected from pores, pits, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, fins, ridges, cliffs, pyramids, and inverted pyramids, and the powder particles have a diameter of 0.01 to 10,000 microns. Any suitable particles provided herein are optionally utilized.

[0016] In some embodiments, provided herein are functionalized crystalline, polycrystalline, semi-crystalline, or amorphous (e.g., semiconductor or insulator) particles, the particles comprising one or more structures selected from pores, pits, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, fins, ridges, cliffs, pyramids, and inverted pyramids, and the powder particles have diameters between 0.01 and 10,000 microns, and wherein at least a portion of the particle crystal lattice is altered relative to an otherwise equivalent particle not functionalized with one or more structures. In some embodiments, at least a portion of the particle crystal lattice is isotopically expanded and / or contracted. In certain embodiments, at least a portion of the particle crystal lattice is anisotropically expanded and / or contracted. In some embodiments, the particle crystal lattice is anisotropically expanded and / or contracted relative to an otherwise equivalent particle not functionalized with one or more structures. <111> and / or <311> The anisotropic expansion and / or contraction is at least 0.1% along the crystallographic direction of the one or more structures. In certain embodiments, the band structure is altered for at least a portion of the particle relative to an otherwise equivalent particle that is not functionalized with one or more structures. Any suitable particle provided herein is optionally utilized.

[0017] Provided herein in some embodiments are methods of modifying the band structure of at least a portion of a particle, the process comprising providing a surface of the particle (e.g., by any one of the processes claimed) with one or more structures selected from pores, depressions, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, fins, ridges, cliffs, pyramids and inverted pyramids (e.g., on the surface thereof), wherein the powder particles have a diameter of 0.01 to 10,000 microns, and wherein at least a portion of the particle crystal lattice is isotopically and / or anisotropically expanded and / or contracted relative to other comparable particles that are not functionalized with the one or more structures. In certain embodiments, the particle crystal lattice is isotopically and / or anisotropically expanded and / or contracted relative to other comparable particles that are not functionalized with the one or more structures. <111> and / or <311> 1%。 Any suitable particle provided herein is optionally utilized.

[0018] In some embodiments, provided herein are kits (e.g., for lysis of one or more cells within a chamber thereof), the kits comprising a container and one or more functional crystalline, polycrystalline, semi-crystalline, or amorphous powder particles of a semiconductor or insulator, where the powder particles (e.g., optionally) comprise one or more structures selected from pores, pits, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, fins, ridges, cliffs, pyramids, and inverted pyramids, and where the powder particles have a diameter between 0.01 and 10,000 microns, and the container comprises a chamber, and where the one or more functional particles are configured within the chamber. In certain embodiments, provided herein (e.g., for lysis of one or more cells within the chamber), the vessel comprising a chamber, the chamber comprising an interior surface or other functional surface, the vessel comprising one or more functional crystalline, polycrystalline, semi-crystalline, or amorphous semiconductor or insulator powder particles in (embedded in) or on its interior surface, where the powder particles (e.g., optionally) comprise one or more structures selected from pores, pits, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, fins, ridges, cliffs, pyramids, and inverted pyramids, and where the powder particles have a diameter of 0.01 to 10,000 μm. In some embodiments, the crystalline, polycrystalline, semi-crystalline, or amorphous powder particles are crystalline, polycrystalline, semi-crystalline, or amorphous powder particles of an element or compound selected from Group IVA elements, Group IV-VI compounds, Group II-IVB compounds, Group I-VII compounds, Group II-VI compounds, Group III-V compounds, Group IV-IV compounds, transition metal oxides, and compounds containing three or more elements. In certain embodiments, the particles further comprise a film coating, chemical functionalization, dopant, nanoparticle decoration, or surface termination. In some embodiments, the functionalized particles are configured within a surface of the container. In certain embodiments, the functionalized particles are not embedded in another material or surface, such as in a loose powder form. In some embodiments, the functionalized particles mechanically bond, chemically bond, interact, or react with elements, compounds, molecules, and particles.In certain embodiments, the functionalized particles extract contaminants from a liquid or gas, catalyze or enhance a chemical reaction, lyse cells, remove microorganisms from a liquid or gas, or any combination thereof.

[0019] In some embodiments, provided herein are bulk composites (e.g., articles of manufacture) comprising one or more functional crystalline, polycrystalline, semicrystalline, or amorphous semiconductor or insulator powder particles (e.g., a bulk comprising one or more particles configured below its surface), where the powder particles optionally comprise one or more structures selected from pores, depressions, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, fins, ridges, cliffs, pyramids, and inverted pyramids, and where the powder particles have a diameter of 0.01 to 10,000 μm. In certain embodiments, the crystalline, polycrystalline, semicrystalline, or amorphous powder particles are crystalline, polycrystalline, semicrystalline, or amorphous powder particles of an element or compound selected from Group IVA elements, Group IV-VI compounds, Group II-IVB compounds, Group I-VII compounds, Group II-VI compounds, Group III-V compounds, Group IV-IV compounds, transition metal oxides, and compounds containing three or more elements. In some embodiments, the powder particles include one or more crystal grains. In certain embodiments, the powder particles consist of a single crystal grain. In some embodiments, the powder particles have a diameter of 0.1 to 1,000 μm. In certain embodiments, the powder particles include two or more structures selected from pores, depressions, craters, nanowires, cones, pinnacles, pillars, corals, fins, ridges, cliffs, pyramids, and inverted pyramids. In some embodiments, the one or more particle structures are submillistructures. In certain embodiments, the one or more particle structures are selected from microstructures and nanostructures. In certain embodiments, the average diameter of the smallest 30% of the powder particles is 200% smaller than the average diameter of the largest 10% of the powder particles. In some embodiments, the surface is antireflective, reflective, adsorptive, conductive, insulating, antistatic, luminescent, antibacterial, non-wetting, hydrophobic, hydrophilic, antifouling, anti-adhesive, anti-slip, or any combination thereof.In certain embodiments, the bulk is antistatic, light absorbing, light reflective, antimicrobial, electrically conductive, insulating, electrically resistive, luminescent, or any combination thereof. In some embodiments, at least a portion of the bulk material is removed exposing at least a portion of one or more functional particles (e.g., or functional particles in the bulk are exposed to or on the surface of the bulk material or otherwise).

[0020] In certain embodiments, any submillistructure provided herein has a dimension less than 500 μm, less than 200 μm, less than 150 μm, less than 100 μm, less than 50 μm, etc., such as at least 1 nm, at least 2 nm, at least 5 nm, at least 25 nm, at least 50 nm, at least 100 nm, etc.

[0021] Incorporation by Reference All publications, patents, and patent applications mentioned in this specification are herein incorporated by reference to the same extent as if each individual publication, patent, or patent application was specifically and individually indicated to be incorporated by reference. [Brief description of the drawings]

[0022] The novel features of the invention are set forth with particularity in the appended claims. To better understand the features and advantages of the present invention, reference should be made to the following detailed description that sets forth illustrative embodiments in which the principles of the invention are utilized and the accompanying drawings in which: [Figure 1] 1 provides exemplary graphical cross-sectional representations of structures that may decorate functional powder particles, including nanowires / pillars, cones, pyramids, inverted pyramids, pits, pores, and hybrids including pyramids and nanowires. The structures and particles are not to scale and are not limited to these examples. [Diagram 2]Figure 2 shows scanning electron microscopy (SEM) images of heterofunctional powder particles containing depressions and pores. The particles were prepared by the method described in Example 2 (Ag metal-assisted chemical etching (MACE) of Si crystalline particles). Image (a) shows a top view of the heterofunctional particles, and image (b) is an enlarged view of image (a). Image (c) shows an enlarged view of the depressions shown in (b), showing the pore structure within the depressions. [Diagram 3] Figure 3 shows SEM images of the porous functional powders prepared by Ag-MACE of Si crystalline particles. Image (b) is an enlarged view of image (a). [Figure 4] Figure 4 shows SEM images of nanowire-containing morphologies. The particles were prepared by Ag-MACE of Si crystalline particles. The nanowires were formed when the etchant was static during Ag-MACE. Sections of the particles were devoid of nanowires because they were broken off during normal processing. [Diagram 5] FIG. 5 shows functionalized powder particles containing rock pillar nanostructures. The particles were prepared by Ag-MACE of Si crystalline particles. Image (a) shows the functionalized powder particle as imaged by SEM. Image (b) shows a magnified view of the functionalized powder particle as imaged by SEM. The irregular interconnected structure of the rock pillars can be seen. Image (c) shows a magnified view from above of the irregular interconnected rock pillar structure as imaged by SEM. Image (d) shows a cross-section of the functionalized powder particle containing rock pillar nanostructures at the surface. A thin Pt coating can be seen on the structure in front. [Figure 6] 6 shows an exemplary cross-sectional view of a heterofunctional nanowire. On the left is a porous nanowire, and on the right is a nanowire with smaller secondary nanowires extending outward from the original nanowire. Structures and features are not to scale. [Figure 7] Figure 7 shows a cross-sectional view of the nanostructuring geometry on a wafer or substrate. The nanowires and wafer are not to scale. [Figure 8]Figure 8 shows a cross-section of a composite containing a small number of functional powder particles embedded in a plastic or other medium. The particles and nanostructuring are not to scale. The illustrated structure is omnidirectional. [Figure 9] FIG. 9 shows cross-sectional views of several possible configurations for integrating functional powder particles into a coating or composite. Diagram (a) shows functional powder particles on the surface of a binder or adhesive on a substrate or bulk medium. Diagram (b) shows functional powder particles completely embedded in a substrate or bulk medium. Diagram (c) shows functional powder particles embedded and at the surface of a substrate or bulk medium. Structures and features are not to scale. Configurations are not limiting. [Figure 10] Figure 10 shows a representation of functional powder particles embedded within fibers. Structures and features are not to scale. [Figure 11] FIG. 11 shows an example of a piezoelectric device utilizing functionalized powder particles and applied AC voltage. The device design is not limited to this depiction. Features and structures are not to scale. [Figure 12] Figure 12 shows SEM images of (a) Ag and (b) Cu nanoparticles on the surface of the powder particles after deposition and cleaning with DI-H2O. Multiple Ag particle size domains are seen in image (a). Cubic and organic shaped Cu particles are seen in image (b). [Figure 13] FIG. 13 shows SEM images of nanoparticles decorating the surface of functionalized powder particles. Image (a) shows an SEM image of Ag nanoparticles decorating the surface of the indentations of functionalized powder particles prepared by Ag-MACE of Si crystalline particles. Image (b) shows an SEM image of a Si powder particle containing pores and Ag nanoparticles. Image (c) shows an SEM image of a Si powder particle containing pores and Ag nanoparticles. The pores seen in (c) are smaller than in (b), and the Ag nanoparticles in (c) are larger than in (b). [Figure 14] FIG. 14 shows a schematic proposed process for the synthesis and application of functional powder particles. [Figure 15]Figure 15 shows an SEM image of functional particles containing depressions and pores decorated with Cu nanoparticles. The particles were prepared by Cu-MACE of Si crystalline particles. [Figure 16] FIG. 16 shows SEM images of morphologies containing coral structures. The particles were synthesized by Ag-MACE of Si crystalline particles. These morphologies were demonstrated to have antibacterial properties. Image (a) shows particles containing coral structures, (b) shows a top-down close-up of the coral structures seen in (a), and (c) shows a side-view of the coral structures seen in (b). The observation angle shows the rough and intricate coral structures. The images display the intricate coral tissue and the interconnected structures formed. [Figure 17] Figure 17 shows SEM images of morphologies including coral structures. The particles were synthesized by Ag-MACE of Si crystalline particles. Image (a) shows the irregular coral structures, and (b) shows a cross-section of the coral structures seen in (a). [Figure 18] Figure 18 shows SEM images of heterofunctional morphologies including pyramidal and coral structures prepared by sequential etching of Si particles. The particles were first synthesized by KOH etching, forming pyramidal structures, as seen in Figure 21, and then further functionalized with Ag-MACE. [Figure 19] FIG. 19 shows SEM images of examples of morphologies of heterofunctional particles including pore nanostructures and dimple nanostructures. Image (a) shows a morphology with triangular opening-like dimples and pores. Functional Si crystal particles were synthesized by Ag-MACE and subsequent nitric acid etching. Image (b) shows square opening pores within the dimples. The morphology was prepared by Cu-MACE. Image (c) shows a microporous surface with triangular opening-like inverted pyramids. The morphology was synthesized by Cu-MACE. [Figure 20]FIG. 20 shows SEM images of morphologies including inverted pyramid structures. These morphologies were prepared by Cu-MACE of Si particles. Image (a) shows a morphology including triangular opening-like inverted pyramids on the surface of a cavity. Image (b) shows a morphology including micro- and nano-scale inverted pyramid structures. Image (c) shows a morphology including convex structures formed from intersecting inverted pyramid structures. [Figure 21] FIG. 21 shows an SEM image of morphologies containing upright pyramidal structures prepared by etching Si particles with 35% (wt / wt) KOH. [Figure 22] 22 shows SEM images of morphologies containing standing pyramidal structures prepared by CE etching with 5% (w / w) NaOH. Image (a) shows a side view of the morphology, and (b) shows a magnified view from above of the pyramidal structures. [Figure 23] FIG. 23 shows SEM images of heterofunctionalized Si particles with intersecting ridge morphology produced via heterofunctionalization involving initial etching with 1% (wt / wt) KOH followed by sequential etching of Ag-MACE. [Figure 24] 24 shows SEM images of the surface of functionalized SiC particles (average diameter 40 μm) prepared by CE etching with HF and HNO3 (3:1 v / v). Image (a) shows a morphology that includes intersecting fin structures, and (b) shows a top view of a morphology that includes wall structures. [Diagram 25] Figure 25 (a) shows X-ray (Cu Kα1) powder diffraction data of unfunctionalized and functionalized crystalline Si powders measured using a Rigaku Ultima IV 3 kW X-ray diffractometer system. The functionalized powders were prepared by the method described in Example 7. A shift in peak position was observed for the Si(111) and Si(311) peaks of the functionalized powders. <111> and <311> Table (b) shows the peak fitting results. [Figure 26]FIG. 26 shows X-ray (Cu Kα1) powder diffraction data of unfunctionalized crystalline SiC powder (average diameter 40 μm) containing both α- and β-crystalline forms measured using a Rigaku Ultima IV 3 kW X-ray diffractometer system. [Figure 27] FIG. 27 shows contact angle measurements of ABS plastic substrates functionalized via attached functionalized Si particles, functionalized SiO particles, and non-functionalized Si particles. Polished Si wafers and bare ABS substrates are shown for comparison. DI-H2O contact angle measurements were performed on a Rame-Hart Model 200 Standard Contact Angle Goniometer. The functionalized ABS plastic substrates were prepared by the method described in Example 16 and had 100% coverage of particles on the examined surface. (a) shows the average contact angle measurement results. Sample 1 coating contains functionalized Si particles prepared by the method described in Example 11, Sample 2 contains functionalized Si particles prepared by the method described in Example 2, Sample 3 contains functionalized Si particles prepared by the method described in Example 7, Sample 4 contains functionalized SiO particles prepared by the method described in Example 13, and Sample 5 contains non-functionalized Si particles (average diameter 45 μm). (b) shows an exemplary side view of a DI-H2O drip on the Sample 3 surface. [Figure 28] FIG. 28 shows the attenuated total reflectance infrared spectra of the C-H modes of symmetric and asymmetric vibration for (A) unfunctionalized Si powder, (B) chemically functionalized Si powder, (C) structurally functionalized Si powder, and (D) chemically and structurally functionalized Si powder, measured using a Nicolet iS50 FT-IR spectrometer. [Figure 29]Figure 29 shows live / dead fluorescence microscopy composite Z-stack example images of E. coli on a nanostructured antimicrobial surface coating on an ABS plastic substrate prepared by the method described in Example 16. Antimicrobial functionalized particles are seen in the background and the rod-shaped features are stained E. coli. After 1 hour of growth at 37°C on the nanostructures, 89±6% of the cells were found to be dead. [Diagram 30] FIG. 30 illustrates a method for lysing cells using functionalized powder. Diagram (a) shows a container containing functionalized particles, (b) shows a solution containing cells added to the container from (a), and (c) shows stirring of the solution containing cells and functionalized particles. The cells in the solution were lysed upon interaction with the functionalized particles. Diagram (d) shows extraction of the solution containing components of the cells. The design of the method is not limited to this depiction. Features and structures are not to scale. [Diagram 31] Figure 31 shows the percentage reduction of viable cells by general bacterial count following the lysis protocol described in Example 25. Treatment (A) and treatment (B) contain structurally functionalized powder particles, (C) contains non-functionalized (average diameter 45 μm) Si powder particles, and (D) contains no powder as a control. The initial bacterial culture population was 5.3×108 / mL and the method is illustrated in Figure 30. [Diagram 32] Figure 32 shows a table of etch depths of functionalized particles prepared by Ag-MACE with different etch durations and agitation speeds. The etch depths were defined by focused ion beam (FIB) cross-sectioning and SEM. The data demonstrate the effect of agitation speed and etch time on the etch depth of functionalized Si particles prepared by otherwise identical conditions. [Diagram 33] 33 shows SEM images of functionalized surfaces produced on amorphous SiO particles using Ag-MACE. Image (a) shows a coral structure, (b) is a close-up of the structure shown in (a), (c) shows a rock pillar structure, and (d) is a close-up of the structure shown in (c). [Diagram 34]34 shows X-ray (Cu Kα1) powder diffraction data of unfunctionalized and functionalized (Sample A) amorphous SiO powders (particle diameters are 38-45 μm) prepared by the method described in Example 13, measured using a Rigaku Ultima IV 3 kW X-ray diffractometer system. The broad peaks centered around 24° and 50° 2θ indicate that the crystal structure of the SiO particles is amorphous. [Diagram 35] FIG. 35 shows an SEM image of a functional surface containing a coding structure on Ge particles, prepared by the method described in Example 15. [Diagram 36] Figure 36 shows SEM images of functionalized heterofunctional surfaces including code structures and triangular aperture-like recess structures on Ge particles prepared by the method described in Example 15. Image (b) is an enlarged view of the structures shown in image (a). [Figure 37] FIG. 37 shows the UV-VIS reflectance data of several surfaces measured at 45° incidence angle using a Shimadzu UV-2401 UV-VIS spectrophotometer. Sample (A) is a polished Si wafer, and sample (B) is a bare ABS substrate, shown for comparison. Samples (C), (D), (E), (F) are functionalized substrates prepared by the method described in Example 16. Sample (C) is an ABS plastic substrate coated with functionalized Si particles, prepared by the method described in Example 11. Sample (D) is an ABS plastic substrate coated with functionalized amorphous SiO particles, prepared by the method described in Example 13. Sample (E) is an ABS plastic substrate coated with heterofunctionalized Si particles containing pits and pores, prepared by the method described in Example 2. Sample (F) is an ABS plastic substrate coated with non-functionalized (average diameter 45 μm) Si particles. The particle surfaces of samples (C), (E), and (F) have similar chemical compositions and crystal structures as sample (A). Different surface morphologies result in different visible light reflectance spectra. [Figure 38]Figure 38 shows optical photographs of several sample surfaces. (A) is a bare ABS plastic substrate, and (B), (C), (D) are coated ABS plastic substrates prepared by the method described in Example 16. Sample (B) is coated with heterofunctional Si particles containing pits and pores prepared by the method described in Example 2. Sample (C) is coated with functionalized amorphous SiO particles prepared by the method described in Example 13. Sample (C) is coated with functionalized Si particles prepared by the method described in Example 11. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Methods for functionalizing particles In some aspects, the present disclosure provides a method of forming structures on powder particles. FIG. 14 provides a conceptual diagram of an exemplary method of forming structures on powder particles. In some embodiments, the method includes the steps of: (a) providing one or more (e.g., crystalline, polycrystalline, semi-crystalline, amorphous) (e.g., semiconductor or insulator) powder particles; (b) (e.g., optionally) removing surface contaminants from the one or more powder particles; (c) (e.g., optionally) removing oxides from the one or more powder particles; and (d) forming (e.g., of a first type) structures on the one or more powder particles, thereby forming one or more homofunctional powder particles. and (e) (e.g., optionally) forming (e.g., of a second type) structures on the one or more homofunctional powder particles, thereby forming one or more heterofunctional powder particles, where the first and second type structures are (e.g., optionally) selected from the group consisting of pores, pits, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, grooves, fins, ridges, cliffs, pyramids and inverted pyramids.

[0024] In some embodiments, the present disclosure provides a method of forming structures on powder particles, the method comprising providing one or more (e.g., crystalline, polycrystalline, semi-crystalline, amorphous) (e.g., semiconductor or insulator) powder particles, and forming a first type of structure on the one or more powder particles, thereby forming one or more homofunctional powder particles. The (e.g., first type) structure may be selected from the group consisting of a pore, a pit, a crater, a nanowire, a cone, a pinnacle, a pillar, a coral, a cord, a wall, a groove, a fin, a ridge, a cliff, a pyramid, and an inverted pyramid.

[0025] In some embodiments, the present disclosure provides a method of forming structures on powder particles, the method comprising: (a) providing one or more (e.g., crystalline, polycrystalline, semi-crystalline, amorphous) (e.g., semiconductor or insulator) powder particles; (b) removing surface contaminants from the one or more powder particles; (c) (e.g., optionally) removing oxides from the one or more powder particles; (d) forming (e.g., a first type) structures on the one or more powder particles, thereby forming one or more homofunctional powder particles; and (e) forming (e.g., a second type) structures on the one or more homofunctional powder particles, thereby forming one or more heterofunctional powder particles, where the first type and / or second type structures are (e.g., optionally) selected from the group consisting of pores, depressions, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, fins, ridges, cliffs, pyramids, and inverted pyramids.

[0026] The powder processing methods described herein differ substantially from typical methods used to functionalize wafers or other substrates. The increased surface area of ​​powders compared to other substrates may alter the reaction characteristics, including kinetics and chemical and particle dynamics of the functionalization reaction. In some examples, the chemical reactions used to create nanostructures on the surface of powder particles may increase the solution temperature due to reaction exotherm and fast kinetics, which may alter the reaction rate. In contrast, the same reaction on a wafer may result in negligible variation in solution temperature due to the low surface area of ​​the wafer. Exposed crystallographic planes or junctions may affect the functionalization process and the resulting morphology. In some examples, particle formation factors provide a greater number and a greater variety of exposed crystallographic planes or junctions compared to wafers. Agitation, or stirring, of the reaction solution may affect the chemical reactions of the powder and the wafer differently, resulting in different functionalization. In some examples, the powder is moving in the solution, which may alter the movement of catalyst nanoparticles into the powder particles and / or the dissolution of materials from the powder. The various morphologies may be formed due to differences in catalyst kinetics as a result of differences in motion between the powder particles and the wafer.

[0027] The methods described herein may be carried out at room temperature and atmospheric pressure. In some embodiments, pressure and temperature may be adjusted to change the structure and morphology present on the surface of the powder particles. The reactions described herein may be carried out in open or closed reaction vessels.

[0028] powder particles The powder particles of the present disclosure may be crystalline, polycrystalline, semi-crystalline, or amorphous. Preferably, the powder particles are crystalline or amorphous. The particles may be solid or may contain porosity and may be of regular or irregular shape. The powder particles may be crystalline particles of an element or mixture. Preferably, the particles are selected from the group consisting of Group IVA elements, Group IV-VI compounds, Group II-IVB compounds, Group I-VII compounds, Group II-VI compounds, Group III-V compounds, Group IV-IV compounds, transition metal oxides, and compounds containing three or more elements. The powder particles may be composed of semiconductor or insulator elements or compounds, such as Si, Ge, Sn, CuCl, CaO, MgO, GaAs, GaN, BN, BP, AlN, InN, InP, SiO, and SiC.

[0029] The powder particles of the present disclosure may include one or more grains. Optionally, the particles consist of a single grain. The powder particles may consist of two, three, or four or more grains held in intimate physical contact. The powder particles may be irregularly shaped, but have an average effective diameter based on the longest and shortest aspect of the particle. The average effective diameter of the particles may be 0.01 μm to 10,000 μm, such as 0.1 μm to 10,000 μm, or 0.1 μm to 1,000 μm. The average effective diameter of the particles may be at least about 0.01 μm, 0.1 μm, 1 μm, 10 μm, 100 μm, 1,000 μm, 10,000 μm, or more. The average effective diameter of the particles may be about 10,000 μm, 1,000 μm, 100 μm, 10 μm, 1 μm, 0.1 μm, 0.01 μm, or less. Optionally, the average effective diameter of the powder particles may be 0.1 μm to 100 μm, 0.1 μm to 10 μm, 1 μm to 10,000 μm, 1 μm to 1,000 μm, 1 μm to 100 μm, 10 μm to 10,000 μm, 10 μm to 1,000 μm, or 100 μm to 10,000 μm. The average effective diameter and size distribution of the powder particles may be selected based on the desired properties and application of the modified particles.

[0030] A population of powder particles may have a characteristic size distribution. The size distribution may be monomodal, bimodal, trimodal, or multimodal. The size distribution may be determined based on a characteristic size, e.g., average diameter, of the powder particles. The size distribution of the powder may be determined by sieving the powder particles. The size distribution of the powder particles may be defined such that about 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or 95% of the particles are within 50% of the average size of the particles. The size distribution of the particles may be defined such that at least about 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or 95% or more of the particles are within 50% of the average size of the particles. The size distribution of the particles may be defined such that no more than about 95%, 90%, 80%, 70%, 60%, 50%, 40%, 30%, 20%, or 10% of the particles are within 50% of the average size of the particles. A particular particle size distribution may be associated with a particular physical property of the functional powder material.

[0031] Pre-etching preparation Prior to forming structures on the powder particles, it may be advantageous to remove surface contaminants from one or more powder particles. Surface contaminants may include any organic or inorganic gas, liquid, or solid other than the desired material deposited on the surface of the powder particles. The powder particles may be placed in a series of baths or solutions having one or more solvents. Optionally, one or more powder particles are placed in a solvent bath, for example, an acetone bath, for at least 10 minutes. The powder particles may further be placed in a second solvent bath, for example, a methanol or ethanol bath, for at least 10 minutes. The step of removing surface contaminants from the powder particles may include ultrasonic treatment. In some embodiments, the surface cleaning may be performed by immersing the powder in an acid bath or an acid bath enhanced with an oxidizing agent, which may be performed at room temperature or at an elevated temperature. Each of the chemical baths may include further successive treatments. For example, a chemical bath with acetone or a chemical bath with ethanol may include agitation for at least 10 minutes followed by ultrasonic treatment for at least 10 minutes. In some embodiments, the powder particles may be placed in a solvent solution that is both simultaneously stirred and sonicated to keep the powder in suspension for at least 10 minutes. In some embodiments, surface contaminants may be removed from one or more powder particles via extended heating at temperatures of 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C or higher. Heating may occur in one or more of a variety of gaseous environments. In some embodiments, one or more powder particles may be heated in a vacuum at a pressure of 100 mbar or less. The powder particles may be heated in a gaseous environment that includes air, N2, CO2, He, H2, Ar, or mixtures thereof.

[0032] The method of the present disclosure may also include removing oxides from one or more powder particles. One or more powder particles may be washed with an acidic or basic solution. For example, the powder particles may be washed in a bath containing a mixture of HF (>1M) and deionized H2O (DI-H2O) for at least 5 minutes. In some embodiments, the bath may be buffered by adding NHF to the HF solution. In some embodiments, the bath may be illuminated to photo-enhance dissolution of oxides and other surface atoms. The wavelength and intensity of the light may be varied depending on the chemistry of the powder particles. The powder particles may be rinsed with a rinsing agent (e.g., DI-H2O) after the chemical bath. The soaked powder particles may be dried and flushed with a gas. The flushing gas may include N2, He, H2, or another gas depending on the desired surface chemistry. The powder particles may be thermally annealed following the bath preparation to reconstruct surface atoms and evaporate residual surface moisture. In some embodiments, thermal annealing may be used instead of the chemical bath method described above. The powder particles may be immersed in an ion-rich solution after bath treatment or thermal annealing. The ion species is selected to change the surface chemistry depending on the desired application of the particles. In some embodiments, a thorough wash with a rinsing agent (e.g., DI-H2O) may be performed after the ion-rich solution bath.

[0033] Etching Method The methods described herein typically include forming a first type of structure on one or more powder particles, thereby forming one or more homofunctional powder particles. In some embodiments, the method may further include forming a second type of structure on one or more homofunctional powder particles, thereby forming one or more heterofunctional powder particles. The forming step may include forming structures on the surface or within the pores of the powder particles. The forming method may be selected based on the desired bulk structure and surface morphology of the powder. The specific structural modification may include single or multi-process etching by plasma, gas or solution methods. For example, the method of making functional powder particles may include a repeated sequence of metal assisted chemical etching (MACE) followed by chemical etching (CE). Optionally, MACE may be performed several times consecutively without CE. Optionally, CE may be performed after MACE. The sequence of various etching methods may be changed to create different morphologies of surface structures. The powder particles may be rinsed with a rinsing agent (e.g., DI-H2O), flushed with a gas such as N2, He or H2, and / or thermally annealed following any etching method to remove any surface foreign matter. Optionally, the particles may be rinsed with a solvent such as methanol, ethanol or acetone.

[0034] Metal-assisted chemical etching (MACE) typically includes two main steps: 1) deposition of metal nanoparticles on the powder surface, and 2) etching in an acid or basic bath. The two steps may optionally be performed simultaneously in a single vessel. Optionally, the deposition and etching processes may be performed independently. In isolation, deposition of metal nanoparticles may be performed once or several times before etching. Etching may be performed once or several times. Optionally, the solution may be stirred or agitated through the use of a magnetic stir bar, overhead stirrer, circulating pump, impeller, or other mixing or stirring device.

[0035] Deposition of metal nanoparticles on powder particles for the MACE process may occur in a solution containing metal ions such as acid or base, DI-H2O, and (e.g., precious or rare metal) ions. For example, HF may be used at a concentration of at least 0.1 M. One or more species of metal ions may be used, including, for example, Ag. A precious metal salt such as AgNO3 may be used to introduce the metal ions into the bath. In some embodiments, other metal salts, including but not limited to, Fe(NO3)3, Cu(NO3)2, HPtCl6, K2PtCl6, HAuCl4, or RhCl3, may be used instead of or in concert with AgNO3. Metal ions may be introduced into the bath solution by other methods, including electrolysis. The temperature, duration, stirring and agitation rate, pH, chemical composition, amount, metal ion concentration, and base or acid concentration of the solution may be adjusted to control the size and surface coverage of the nanoparticle deposition. When two or more species of metal ions are deposited on the powder particle surface, they can be deposited simultaneously or in a single step at the same or different surface concentrations. In some embodiments, the solution may be illuminated to change the deposition behavior of the metal nanoparticles. The wavelength and intensity of the light may be varied depending on the physical and chemical properties of one or more powder particles. The powder particles may be thermally annealed after MACE to change the surface coverage of the metal nanoparticles.

[0036] Alternatively, MACE can be carried out in a solution containing an acid or base, an oxidizing species, and DI-H2O. In some embodiments, the DI-H2O can be partially or completely replaced by another solvent, such as methanol, ethanol, isopropyl alcohol, or acetone. For example, HF can be selected as the acid, preferably at a concentration greater than 4M, and H2O2 can be selected as the oxidizing agent. In some embodiments, HF can be replaced by another acid, such as H3PO4, HCl, or a base, such as NHF. The oxidizing species can be selected from H2O2, O2 gas, ozone, H2SO4, H2S2O8, NaClO, NaClO4, KMnO4, and Fe(NO3)3. Optionally, the reagents can be added to the solution over a period of time. The acid or base concentration, oxidizing agent concentration, duration of dissolution, rate of stirring and agitation, pH, chemical composition, amount, rate of chemical addition, and temperature can be varied to control the structure and morphology of the etching performed on the powder particle surface. In some embodiments, the solution may be illuminated to alter the dissolution of the particles. The wavelength and intensity of the light may be varied depending on the physical and chemical properties of one or more of the powder particles, and the desired surface structure and morphology. Excess metal nanoparticles may be removed from the powder particle surface. For example, a solution of HNO3 and DI-H2O may be used to remove the metal from the particle surface. In some embodiments, the metal may be removed from the surface of the particles using an acidic solution, e.g., sulfuric acid, perchloric acid, aqua regia. In some embodiments, the removal of the metal nanoparticles may be achieved using electrochemical methods, suitable chemical methods, or a combination of both methods. In some embodiments, the recovered metal nanoparticles may be restored and reused for further use.

[0037] In carrying out any of the subject methods, chemical etching (CE) of one or more of the powder particles may be performed before or after the metal-assisted chemical etching to prevent. CE typically includes any method for selectively removing surface material using means that are chemical and not mechanical in nature. The CE step may be performed once or several times in the subject methods. The CE method may include an acid or base solution with the treated powder particles. For example, the CE bath may include KOH and DI-H2O. In some embodiments, the KOH may be replaced with an acid or base species such as NHF, HF, NaOH, LiOH, RbOH, CsOH, NH4OH, Sr(OH)2, Ca(OH)2, Ba(OH)2, tetramethylammonium hydroxide, or HBr. The chemical concentrations, solution temperatures, durations, stirring and agitation rates, pH, chemical composition, amounts, and rates of chemical addition may be varied depending on the desired surface structure and morphology. In some embodiments, the solution may be illuminated to enhance surface dissolution of the powder particles. The wavelength and intensity of the light may be varied depending on the physical and chemical properties of the powder particle or particles.

[0038] Further Processing After the formation of one or more structures on the powder particles, the resulting homo- or hetero-powder particles may be subjected to one or more additional processes. The combination of optional additional processes described below may be performed in any order and repeated any number of times. In some examples, the optional additional processes are performed before the functionalized powder particles are incorporated into a product. Alternatively, the optional additional processing may be performed after the functionalized powder particles are incorporated into a product.

[0039] Additional processing methods include methods of film coating or plating one or more powder particles. Film coating or plating can include any process that results in uniform, semi-uniform, non-uniform, or patterned deposition of a thin film of material covering the entire surface or a portion of the surface of the powder particle. For example, vapor deposition can be used to deposit the thin film. In some embodiments, chemical baths, electrochemical methods, spin coating, dip coating, spraying, roll-to-roll coating, or lithographic methods can be used.

[0040] Additional processing includes methods to chemically functionalize the surface of one or more powder particles. Chemical functionalization can include any process that creates reactive or non-reactive fields on the surface of one or more powder particles. For example, the surface of the powder particles can be bonded with an active antimicrobial chemical agent, such as chlorhexidine digluconate or (3-aminopropyl)triethoxysilane. Alternatively, the surface of the particles can be functionalized through reaction with functionalizing compounds, such as silane compounds, including but not limited to octadecyltrichlorosilane or 1H,1H,2H,2H-perfluorodecyltriethoxysilane, to create a highly hydrophobic surface that can also improve the binding of the particles to a substrate. In some embodiments, the surface can be functionalized with a dispersant or peptide. In some embodiments, the surface of the particles can be functionalized to aid in the binding or adhesion of the particles to a product or medium. For example, diethoxydiphenylsilane, allyltrichlorosilane, triethoxy-p-tolylsilane, allyltriethoxysilane, vinyltrimethoxysilane, or other derivatized silanes can be used to bond particles in polymeric media through covalent or non-covalent interactions. Powder particle surfaces can be functionalized with more than one chemical species depending on the material properties desired for the selected application. Chemical functionalization can include methods to change properties such as surface energy, surface area, surface roughness, density profile, reflectivity, optical constants, electrostatic charge, band gap, shear modulus, plasticity, specific weight, coefficient of friction, acoustic properties, thermal properties, optical properties, electrical properties, chemical properties, non-covalent interactions, photoluminescence, light absorption, hydrophobicity, and hydrophilicity.

[0041] Other additional processing may include methods of doping one or more powder particles via neutron irradiation. Exposure of a powder particle to neutron radiation may change its electronic properties, band structure, or its band gap. Sub-millimeter structures created via methods such as MACE may be sensitive to doping of semiconductor particles. In some instances, nanostructuring prior to neutron irradiation allows for specific structures and morphologies enhanced with desirable electronic properties.

[0042] Another additional treatment may include decoration of one or more powder particles with nanoparticles, as shown in Figures 12, 13, and 15. Nanoparticles may be deposited or dispersed on the surface of the functional powder particles by any method of nanoparticle synthesis. For example, nanoparticles may be deposited in a chemical bath. In some embodiments, nanoparticles may be deposited by vapor deposition. Nanoparticle decoration may be used to change and enhance the physical or chemical properties of the powder particles. Nanoparticles may be used to enhance the antibacterial properties of the powder particles. For example, Ag, Cu, or ZnO nanoparticles may be added to one or more powder particles for their antibacterial activity. Nanoparticles such as Ag, Au, and Cu may enhance the electrical and optical properties of the powder particles. Nanoparticles may decorate the powder particle surface to enhance UV light absorption. For example, Al2O3 or ZnO may enhance the UV light absorption characteristics of the powder particles. Nanoparticles may also be utilized to protect the nanostructures from UV photodegradation. For example, CeO2 nanoparticles may be used as UV protectants.

[0043] structure The present disclosure provides powder particles containing structures, methods for forming these structures, and compositions containing the powder particles. Any structure disclosed herein may refer to submillimeter structures, such as microstructures or nanostructures. Specific examples of types of structures suitable in the present methods and compositions include, but are not limited to, pores, depressions, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, fins, ridges, cliffs, pyramids, and inverted pyramids. Examples of nanostructures that can decorate functional powder particles are shown in FIG. 1.

[0044] Dimples, craters, and pores refer to indentations on a powder particle. Dimples and craters may have a depth-to-diameter ratio of less than 2. The term pore is used to refer to any indentation having a depth-to-diameter ratio of 2 or greater. Pores may, but need not, have two open ends. Dimples, craters, and pores may have openings of geometric or organic shapes. Example images of dimples and pores on particle surfaces are shown in Figures 2, 3, and 19.

[0045] The terms nanowire, pinnacle, and pillar are used interchangeably and refer to elongated structures extending out from a powder particle. A nanowire or pillar may have a height to diameter ratio of 2, 3, 4, 5, 6, 7, 8, 9, 10, or more. A nanowire or pillar may, but need not, have a circular cross-section. A nanowire or pillar may have a similar average cross-sectional area, or a variable cross-sectional area. Examples of nanowires and nanopillars on the surface of a powder particle are shown in FIG. 4. The term cone refers to a pillar structure with a continuously decreasing cross-sectional area from base to tip.

[0046] The term pyramid refers to any structure extending out from a powder particle that decreases in cross-sectional area from base to tip and has three or more sides. Pyramid structures may, but need not, have sharp or flat sides. Pyramid structures may, but need not, have a truncated tip or a flat tip. Examples of pyramidal structures on the surface of a powder particle are shown in Figures 21 and 22.

[0047] An inverted pyramid refers to any concave pyramidal structure that decreases in cross-sectional area from base to tip and extends into a particle with three or more sides. Inverted pyramidal structures may, but need not, have flat sides, sharp angles, or truncated or flat tips. An example of an inverted pyramidal structure on the surface of a powder particle is shown in FIG. 20.

[0048] The term ridges or cliffs refers to protruding, intersecting structures along their length whose cross-sectional width at FWHM (full width at half maximum) is submicron and less than their length. Ridges or cliffs may consist of curved or straight sections along their length. Ridges or cliffs may, but need not, form enclosed, recessed regions. Examples of ridges and cliffs on the surface of a powder particle are shown in FIG. 23.

[0049] The term wall refers to a protruding structure whose length is greater than its height or cross-sectional width and which is of similar width-to-height ratio along its length. A wall may, but need not, have a constant cross-sectional width from base to top. An example of a wall on the surface of a powder particle is shown in Figure 24(b).

[0050] The term fin refers to a protruding structure whose length is greater than its height or cross-sectional width and which is of varying height along its length. The fin may, but need not, have a decreasing cross-sectional area from base to apex. An example of a fin on the surface of a powder particle is shown in Figure 24(a).

[0051] The term cord refers to an elongated convex structure whose height does not exceed the width of the base. The cord may, but need not, have a semicircular cross-sectional shape. The cord may, but need not, be parallel to other cords. An example of a cord on the surface of a powder particle is shown in FIG. 35.

[0052] The term rock pillars refers to laterally interconnected or interconnected protruding pillar-like structures of variable cross-sectional area or shape. Figures 5, 33(c), and 33(d) depict several laterally interconnected nanopillars that may be classified as rock pillars.

[0053] The term coral refers to any elongated structure that is irregular in morphology or non-geometric in shape. For example, an elongated structure whose direction changes along its length and whose cross-sectional area or shape is variable may be called a coral. Corals may, but need not, have interconnected or interconnected features. Any nanostructure or microstructure that cannot be easily classified into other classes of structures may be considered to be a coral. Figures 16, 17, 33(a), and 33(b) depict irregularly formed nanoscale formations that may be classified as corals.

[0054] A single powder particle may include more than one type of structure. In some embodiments, the structures are layered on top of each other as shown in FIG. 6. For example, a powder particle may include nanowires on the side of a pyramid. The nanowires may decorate the side of a pyramid, inverted pyramid, crater, cone, pilaster, coral, cord, wall, fin, ridge, cliff, or other nanowire. The pits and pores may decorate the surface of the nanowire, crater, cone, pyramid, inverted pyramid, coral, cord, wall, fin, ridge, cliff, or pilaster, or other pit and pore. A single powder particle may include any combination of first and second structures. For example, FIG. 18 depicts a particle with a heterofunctional morphology including pyramidal and coral structures. For example, FIG. 2 depicts a particle with overlapping structures including pits and pores. For example, FIG. 36 depicts particles with heterofunctional morphology including cords and triangular aperture-like depressions.

[0055] The structures formed on the powder particles, including the first and second structures, may be characterized by a characteristic dimension. The characteristic dimension may include properties such as length, width, height, diameter, and circumference. The characteristic dimension of the structures formed on the powder particles may be constant or may be variable over the body of the structure. For example, a pyramidal or cone structure may be characterized as having a circumference that decreases from the base to the tip of the pyramid. The structures formed on the powder particles may also have multiple characteristic dimensions, such as length and radius. A particular characteristic dimension, or range of characteristic dimensions, may be related to certain physical properties of the functional powder material. The characteristic dimension of a particular structure may vary on a single particle or may vary from particle to particle.

[0056] The structures formed in the powder particles may have a characteristic dimension of about 1 nm, 10 nm, 25 nm, 50 nm, 75 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1 μm, 10 μm, 100 μm, or 1000 μm. The structures formed in the powder particles may have a characteristic dimension of at least about 1 nm, 10 nm, 25 nm, 50 nm, 75 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1 μm, 10 μm, 100 μm, or 1000 μm or more. The structures formed in the powder particles can have characteristic dimensions of about 1000 μm, 100 μm, 10 μm, 1 μm, 900 nm, 800 nm, 700 nm, 600 nm, 500 nm, 400 nm, 300 nm, 200 nm, 100 nm, 75 nm, 50 nm, 25 nm, 10 nm, 1 nm, or less.

[0057] Two characteristic dimensions of a structure formed on a powder particle may have a particular aspect ratio. For example, the aspect ratio may include the length to width ratio for a particular structure. The aspect ratio may be calculated based on an average value of the characteristic dimensions. For example, a structure with a variable diameter may have an aspect ratio based on the average diameter over the length of the structure. A particular characteristic aspect ratio, or range of aspect ratios, may be related to certain physical properties of the functional powder material. The aspect ratio of a particular structure may vary on a single powder particle or between two different powder particles.

[0058] In some cases, the structures formed on the powder particles may be characterized by more than one characteristic or characteristic dimension. The characteristic or characteristic dimensions may include width, height, depth, spacing, diameter, tip diameter, aperture width, tip-to-tip distance, base diameter, and peak state width. In some cases, the characteristic or characteristic dimension may have a characteristic value or range. The range may be defined by the minimum and / or maximum dimension of the structure dimensions. Table I below displays some approximate characteristic dimensions for various structures of the present invention. The actual observed characteristic dimensions may be about 5%, 10%, 15%, 20%, 25%, or more than or less than the stated characteristic dimension range.

[0059] [Table 1]

[0060] The structure or structures on the functionalized powder particles may be characterized as having an average aspect ratio of about 1:1000, 1:100, 1:10, 1:5, 1:2, 1:1, 2:1, 5:1, 10:1, 100:1, or about 1000:1. The structure or structures on the functionalized powder particles may be characterized as having an average aspect ratio of at least about 1:1000, 1:100, 1:10, 1:5, 1:2, 1:1, 2:1, 5:1, 10:1, 100:1, or about 1000:1. The structures or structures on the functional powder particles may be characterized as having an average aspect ratio of no more than or less than about 1:1000, 1:100, 1:10, 1:5, 1:2, 1:1, 2:1, 5:1, 10:1, 100:1, or about 1000:1.

[0061] The structures on the powder particles may have a characteristic size distribution. The size distribution may be monomodal, bimodal, trimodal, or multimodal. The size distribution may be determined for any characteristic dimension of the structures. For example, functional powder particles functionalized with pillars may have a monomodal pillar length distribution around an average pillar length value. The size distribution of the structures may be determined such that about 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, or 95% of the structures are within 50% of the average size of the structures. The size distribution of the structures may be determined such that at least about 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, or 95% or more of the structures are within 50% of the average size of the structures. The size distribution of the structures may be determined such that no more than about 95%, 90%, 80%, 70%, 60%, 50%, 40%, 30%, 20%, or 10% of the structures are within 50% of the average size of the structures. A particular characteristic structure size distribution may be related to certain physical properties of the functional powder particles. A particular structure size distribution may vary between regions of a single powder particle or between two different powder particles.

[0062] The structures on the particle may have a characteristic surface density. Surface density may be defined as the number of unique structures per unit area. Surface density may be calculated for a single type of structure (e.g., pillars) or may include the density of more than one type of structure (e.g., the total surface density of all structures on a powder particle). A particular characteristic surface density may be related to certain physical properties of the functional powder particle. The surface density of a particular structure may vary between regions of a single powder particle or between two different powder particles.

[0063] The powder particles have a diameter of at least about μm 2 1 structure per μm 2 5 structures per μm 2 10 structures per μm 2 15 structures per μm 2 20 structures per μm 2 25 structures per μm 2 30 structures per μm 2 40 structures per μm 2 50 structures per μm 2 100 structures per μm 2 250 structures per μm 2 500 structures per μm 2 1000 structures per μm 2 The powder particles may have a surface density of 10,000 structures per μm or even more. 2 Approximately 10,000 structures per μm 2 1000 structures per μm 2 500 structures per μm 2 250 structures per μm 2 100 structures per μm 2 50 structures per μm 2 40 structures per μm 2 30 structures per μm 2 25 structures per μm 2 20 structures per μm 2 15 structures per μm 2 10 structures per μm 2 5 structures per μm 2The structure may have a surface density of no more than one structure per square inch, or less.

[0064] Particles of Sensuality In some embodiments, the present disclosure provides homofunctional (e.g., crystalline, polycrystalline, semi-crystalline, or amorphous) (e.g., semiconductor or insulator) powder particles, where the powder particles include one type of structure selected from the group consisting of pores, pits, craters, nanowires, cones, pinnacles, pilasters, corals, cords, walls, fins, ridges, cliffs, pyramids, and inverted pyramids. In some embodiments, the present disclosure provides homofunctional (e.g., crystalline, polycrystalline, semi-crystalline, or amorphous) (e.g., semiconductor or insulator) powder particles, where the powder particles include one type of structure selected from the group consisting of pores, pits, craters, nanowires, cones, pinnacles, pilasters, corals, cords, walls, fins, ridges, cliffs, pyramids, and inverted pyramids. In some embodiments, the present disclosure provides homofunctional (e.g., crystalline, polycrystalline, semicrystalline, or amorphous) (e.g., semiconductor) powder particles, where the powder particles include one type of structure selected from the group consisting of pores, pits, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, fins, ridges, cliffs, pyramids, and inverted pyramids, where the powder particles are not elemental silicon particles. In some embodiments, the present disclosure provides functional (e.g., crystalline, polycrystalline, semicrystalline, or amorphous) (e.g., semiconductor or insulator) powder particles, where the powder particles include sub-millimeter structures and further include film coating, plating, chemical functionalization, dopants, nanoparticle decoration, or surface termination. In other embodiments, the present disclosure provides heterofunctional (e.g., crystalline, polycrystalline, semicrystalline, or amorphous) (e.g., semiconductor or insulator) powder particles, where the powder particles include two or more types of structures. The two or more types of structures may be selected from the group consisting of pores, pits, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, fins, ridges, cliffs, pyramids and inverted pyramids.

[0065] The average effective diameter of the functional powder particles may be 0.01 to 10,000 μm, such as 0.1 to 10,000 μm, or 0.1 to 1,000 μm. Optionally, the average effective diameter of the powder particles may be 0.1 to 100 μm, 0.1 to 10 μm, 1 to 10,000 μm, 1 to 1,000 μm, 1 to 100 μm, 10 to 10,000 μm, 10 to 1,000 μm, or 100 to 10,000 μm.

[0066] A functionalized powder particle may include two or more overlapping structures, such as nanowires on the side of a pyramid. In some embodiments, nanowires may decorate the side of a pyramid, inverted pyramid, cone, pilaster, coral, cord, wall, fin, ridge, cliff, or other nanowire, and pits and pores may decorate the surface of the nanowire, cone, pyramid, inverted pyramid, coral, cord, wall, fin, or pilaster, or pit and pore. A single powder particle may include any combination of first and second structures.

[0067] In some examples, the particles reflect up to an average of 0.1% of the total electromagnetic radiation (e.g., specular and / or diffuse) between 10 nm and 1,050 nm. In some embodiments, the particles may reflect up to an average of 0.01% of the total electromagnetic radiation (e.g., specular and / or diffuse) between 10 nm and 400 nm, up to an average of 0.1% of the total electromagnetic radiation (e.g., specular and / or diffuse) between 300 nm and 1,050 nm, or up to an average of 0.1% of the total electromagnetic radiation (e.g., specular and / or diffuse) between 700 nm and 1,050 nm. In some examples, as seen in FIG. 37, the particles reflect up to an average of 0.03% of the total electromagnetic radiation at a 45° angle of incidence between wavelengths between 190 nm and 900 nm. In some examples, the particles reflect up to an average of 0.046% of total electromagnetic radiation at a 45° angle of incidence between wavelengths of 180 nm and 380 nm, and up to an average of 0.026% of total electromagnetic radiation at a 45° angle of incidence between wavelengths of 380 nm and 740 nm. In some examples, the particles reflect up to 1% of total electromagnetic radiation (e.g., specular and / or diffuse) at wavelengths of 300 nm and 1,050 nm. In some embodiments, the particles may reflect up to 1% of total electromagnetic radiation (e.g., specular and / or diffuse) between 10 nm and 400 nm, up to 1% of total electromagnetic radiation (e.g., specular and / or diffuse) between 300 nm and 1,050 nm, or up to 1% of total electromagnetic radiation (e.g., specular and / or diffuse) between 700 nm and 1,050 nm. In some examples, the particles reflect up to an average of 10% of all electromagnetic radiation (e.g., specular and / or diffuse) between 10 nm and 1,050 nm wavelengths. In some embodiments, the particles may reflect up to 10% of all electromagnetic radiation (e.g., specular and / or diffuse) between 10 nm and 400 nm, up to 10% of all electromagnetic radiation (e.g., specular and / or diffuse) between 190 nm and 900 nm, or up to 10% of all electromagnetic radiation (e.g., specular and / or diffuse) between 700 nm and 1,050 nm.In some examples, the particles reflect up to 25% of the total electromagnetic radiation (e.g., specular and / or diffuse) between 300 nm and 1,050 nm wavelengths. In some embodiments, the particles may reflect up to 25% of the total electromagnetic radiation (e.g., specular and / or diffuse) between 10 nm and 400 nm, up to 25% of the total electromagnetic radiation (e.g., specular and / or diffuse) between 190 nm and 900 nm, or up to 25% of the total electromagnetic radiation (e.g., specular and / or diffuse) between 700 nm and 1,050 nm.

[0068] Physical and chemical properties of functional particles The structure and organization of the functionalized powder particles can change the physical and / or chemical properties of at least a portion of the particles. The properties can be changed radially and / or angularly. Examples of properties and characteristics of powder particles that can be changed by the structure and organization include, but are not limited to, surface energy, surface area, surface roughness, density profile, refractive index, optical constants, electrostatics, band structure, band gap, shear modulus, plasticity, coefficient of friction, specific weight, acoustic properties, thermal properties, optical properties, electrical properties, chemical properties, non-covalent interactions, photoluminescence, light absorption, cell lysis, omniphobicity, hydrophobicity, and hydrophilicity.

[0069] Functionalized powder particles may exhibit altered material properties more easily than similar structurally functionalized common substrates. Structurally functionalized powder particles will be more complex than similar structures on non-particle substrates such as Si wafers. Because functionalized powder particles have a high surface area to volume ratio (or surface area to mass ratio) and are smaller than non-powder particle morphologies, more of the functionalized powder particle mass or volume is composed of sub-millimeter structures. Sub-millimeter structures on powder particles (e.g., crystalline, polycrystalline, semi-crystalline, or amorphous) may exhibit a wider range of orientations than structures on non-particle substrates due to functionalization of the entire powder surface. Omnidirectional structures may enhance the properties of functionalized powder particles for three-dimensional applications. Functionalized powder particles are characterized by a wider range of physical length scales than on non-particle substrates. The wider range of length scales may provide a wider range of material properties in functionalized powder particles.

[0070] Functionalized (e.g., crystalline, polycrystalline, and semi-crystalline) powder particles can have altered crystal lattice and band structures from non-functionalized particles or non-functionalized substrates. For example, FIG. 25 shows X-ray (Cu Kα1) powder diffraction data from non-functionalized crystalline Si powder and functionalized crystalline Si powder prepared via the method described in Example 7 after 90 minutes of etching. These functionalized particles (average diameter of 45 μm) have a structurally functionalized surface with a thickness of 1.5 μm. This structural functionalization results in lattice expansion and contraction of the entire functionalized particle, including the hard core and the functionalized surface, even though the structural functionalization represents a very small fraction of the particle volume. <111> and <311> The expansion and contraction of the crystal lattice along the directions is evident by the shift in the peak position of the Si(111) and Si(311) peaks, respectively. The change in the crystal lattice structure can alter the band structure compared to non-functionalized particles or non-functionalized substrates, and this is done without changing the bulk chemical composition or introducing bulk crystal defects.

[0071] The functionalized powder particles can change the thermal properties. Thermal expansion and contraction can have a reduced effect on the nanostructures. Cracking and other mechanical failures can be reduced in the functionalized powder particles.

[0072] Multifunctional particles Functionalized particles may form part of a homogeneous mixture of similar particles or a heterogeneous mixture of particles of two or more variants, where one variant may differ from the others in at least one physical or chemical property, such as chemical composition, size, shape, surface modification, type of structure on the surface, type of structure on the subsurface, chemical functionalization, nanoparticle decoration, surface termination, or doping.

[0073] In some embodiments, two or more functional particle variants are mixed together to achieve desired physical properties. For example, a mixture of functional particles containing different elemental or compound species, such as Si or Ge, can be used to provide a mixture with favorable optical properties. The packing density of the particles can be increased by mixing functional particles with different sizes, so that the smaller particles occupy or fill the voids between the larger particles. A mass density gradient can be formed by mixing particles of different sizes. A graded optical index of refraction can also be formed by mixing particles of different sizes. A mixture of particles can be formed, where some particles have durable properties and others have delicate properties. For example, large particles with inverted pyramid structures can be mixed with small particles covered with nanowires. The small particles can occupy the voids between the larger particles so that the more delicate nanowires are protected from mechanical or other destruction.

[0074] These mixtures, either homogeneous or non-homogeneous, can be used in a variety of applications. Examples include filters, such as fluid or gas filters, that include a container containing one or more functional particles. In this example, the functional particles can mechanically or chemically bind, interact, or react with elements, compounds, molecules, particles, or cells as the fluid or gas flows through the filter. Applications of such filters include the extraction of contaminants from fluids or gases, catalysis or enhancement of certain chemical reactions, lysis of cells for intracellular analysis and harvesting of cellular components, and removal of unwanted microorganisms from fluids. This high surface area of ​​functionalized particles allows a larger amount of chemicals to be embedded or decorated per particle than non-functionalized particles. In some embodiments, functionalized powder particles can be utilized in analytical columns. In some embodiments, functionalized powder particles can be modified with functional groups, such as flavor or aroma compounds. In some embodiments, nanoparticles containing flavor or aroma compounds can be embedded or decorated on the surface of the functionalized powder particles. Functionalized powder particles can transfer or replicate nanostructures on other materials. For example, powder particles with nanowires can be used as a mold, stamp, or template to create structures on the surface of a softer material.

[0075] Functional particle complex In some embodiments, the present disclosure provides a surface comprising one or more functional (e.g., crystalline, polycrystalline, semi-crystalline, or amorphous) (e.g., semiconducting or insulating) powder particles, where the powder particles optionally comprise one or more structures selected from pores, depressions, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, fins, ridges, cliffs, pyramids, and inverted pyramids, and the diameter of the powder particles is between 0.01 μm and 10,000 μm. The average diameter of the smallest 30% of the powder particles may be 200% smaller than the average diameter of the largest 10% of the powder particles. Optionally, the average diameter of the smallest 10% of the powder particles may be 200% smaller than the average diameter of the largest 10% of the powder particles, the average diameter of the smallest 1% of the powder particles may be 200% smaller than the average diameter of the largest 10% of the powder particles, the average diameter of the smallest 30% of the powder particles may be 100% smaller than the average diameter of the largest 10% of the powder particles, or the average diameter of the smallest 10% of the powder particles may be 50% smaller than the average diameter of the largest 10% of the powder particles. The surfaces described herein may further include a film that separates the powder particles from the atmosphere. The surface may be antireflective, reflective, antibacterial, hydrophobic, hydrophilic, antifouling, non-stick, or have any physical property or combination of physical properties desired for a selected application.

[0076] One or more functional particles described herein may be used as components or additives in bulk materials, fibers, surfaces, or surface coatings, for example, as shown in FIG. 9. The concentration, distribution (e.g., out-of-plane and in-plane locations) and orientation of the functional particles may be determined separately for a given application. The functional powder particles may alter the interaction with the substrate or medium due to increased surface area compared to non-functionalized particles. For example, the functionalized powder particles may increase chemical or bonding sites compared to non-functionalized particles. The functionalized powder particles may be used to formulate more durable composites. The smaller length scale of the nanostructures may inhibit fracture propagation compared to substrate materials such as semiconductor wafers. In some examples, the reduced density of the functionalized particles may reduce the mass of the composite compared to non-functionalized particles.

[0077] In some examples, one or more functional particles are embedded in the surface such that at least one powder particle is exposed to the atmosphere. In this arrangement, the structure of the embedded functional particles is at least partially exposed at the surface of the matrix, medium, fiber, binder, or adhesive. Optionally, one or more functional particles can be adhered to the matrix, medium, binder, or adhesive such that the particles are fully exposed. The height of the exposed particles can vary, and the height of the particles relative to each other can be uniform or non-uniform. Also, the volume of the exposed particles can vary, and the volume of the particles relative to each other can be uniform or non-uniform. Optionally, one or more functional particles can be adhered to the matrix, medium, binder, or adhesive such that the particles are fully hidden.

[0078] In some examples, one or more functionalized powder particles on the surface of a composite material can impart a wider range of length scales to the composite surface compared to a nanostructured wafer or substrate, which can alter the physical properties of the material, as shown in Figures 7 and 8. For example, a composite comprised of functionalized powder particles in a resin can absorb a wider range of electromagnetic radiation than a non-particulate substrate, such as a semiconductor wafer, due to the presence of nanoscale and microscale features.

[0079] In some instances, one or more partially exposed functional powder particles may alter the mechanical properties of the composite material. Exposed nanostructures at the surface of the composite may be protected from damage due to their orientation relative to the particle core or macrosurface.

[0080] In some examples, one or more functional powder particles on the surface of a composite can increase the surface area of ​​the composite surface. The composite surface area can exceed the surface area of ​​a non-particulate substrate, such as a semiconductor wafer. A composite that includes one or more exposed functional powder particles can have a greater functionality density (surface area of ​​functionality per contact area of ​​particles) when incorporating powder particles with sufficient surface packing density.

[0081] Methods for changing surface features In some examples, the disclosure provides a method of altering a characteristic of a product, the method comprising incorporating one or more functional (e.g., crystalline, polycrystalline, semi-crystalline, or amorphous) (e.g., semiconducting or insulating) powder particles into the product, where the powder particles optionally comprise one or more submillimeter structures selected from pores, pits, craters, nanowires, cones, pinnacles, pillars, corals, cords, walls, fins, ridges, cliffs, pyramids, and inverted pyramids, where the powder particles have a diameter of 0.01 μm to 10,000 μm. The product can be any product described herein, such as a medical device, cookware, appliance, countertop, vehicle, boat, or aircraft. The product may be selected from office consumables, office supplies, electronics, containers, kitchen utensils, cookware, household goods, textiles, hardware, consumer goods, vehicles and marine, filters, pumps, water fixtures, surfaces, furniture, fixtures, equipment, building materials, military equipment, tools, solar cells, currency, medical supplies, medical devices, paper products, manufacturing equipment, food processing equipment, and optical equipment. In some embodiments, the product comprises rubber, plastic, metal, glass, or ceramic. In some embodiments, modifying comprises one or more of decreasing the absorbance of visible light, increasing the absorbance of visible light, increasing the reflectance of light, decreasing the reflectance of light, increasing antibacterial properties, increasing antifouling properties, increasing hydrophobicity, increasing hydrophilicity, increasing electrical conductivity, increasing electrical resistivity, increasing luminescence, increasing surface energy, decreasing surface energy, increasing coefficient of friction, and decreasing coefficient of friction of the product. The incorporating step may include coating the product with the powder particles or embedding the powder particles into the product.

[0082] Antibacterial applications The functionalized particles of the present disclosure may be used to form antimicrobial surfaces. The antimicrobial mode of action may be physical or chemical, including ultraviolet radiation, microwave radiation, and heating. The antimicrobial functionalized particles described herein may exhibit one or more antimicrobial modes of action. In some examples, nanostructures that may provide antimicrobial activity may include nanowires, pinnacles, cones, pores, pillars, corals, cords, walls, fins, ridges, cliffs, pyramids, inverted pyramids, and hybrid structures. The height of the nanowires for antimicrobial activity may be within the range of 10 nm to 5 μm. In some embodiments, the height of the nanowires for antimicrobial activity may be within the range of 10 nm to 200 nm, 50 nm to 500 nm, 100 nm to 1 μm, 250 nm to 2 μm, or 500 nm to 5 μm. The diameter of the nanowires for antimicrobial activity may be within the range of 10 nm to 1000 nm. In some embodiments, they may have a diameter of 10 nm to 100 nm, 50 nm to 250 nm, 100 nm to 500 nm, or 250 nm to 1000 nm. The vertical component of the extension or protrusion of the cones, pores, pilasters, corals, cords, walls, fins, ridges, cliffs, pyramids, inverted pyramids, and hybrid structures for antimicrobial activity may be within the range of 1 nm to 5 μm. In some embodiments, the vertical component of the extension or protrusion of the cones, pores, pilasters, corals, grooves, fins, ridges, cliffs, pyramids, inverted pyramids, and hybrid structures for antimicrobial activity may be within 1 nm to 200 nm, 50 nm to 500 nm, 100 nm to 1 μm, 250 nm to 2 μm, or 500 nm to 5 μm. The width along the narrow dimension of the cross-section of the elongated or convex components of the cones, pores, pillars, corals, grooves, fins, ridges, cliffs, pyramids, inverted pyramids, and hybrid structures for antimicrobial activity can be in the range of 1 nm to 10,000 nm, in some embodiments they can have dimensions of 1 nm to 100 nm, 50 nm to 250 nm, 100 nm to 500 nm, or 250 nm to 1000 nm.

[0083] Physical mode of action: cells may be killed or lysed by physical interactions between the cell membrane and the functionalized particle surface. Antimicrobial activity and effectiveness may depend on the specific type of structures on the particle in contact with the cell membrane. Without wishing to be bound by any particular theory, cells may be killed when the adhesive forces between the functionalized particle and the cell membrane become greater than the cohesive forces of the cell membrane. In some instances, viruses may be captured, immobilized, or inactivated by interactions between the virus and the functionalized particle surface.

[0084] In some examples, cells may be killed when adsorbed onto the surface of functionalized powder particles. The physical mode of cell death may vary depending on whether the surface is hydrophobic or hydrophilic. For example, functionalized powder particles with hydrophobic surfaces may attract the hydrophobic tails of lipids in the cell membrane, causing the extraction of lipid molecules from the cell membrane. If a sufficient amount of lipid is extracted, the cell membrane may rupture, causing cell death. In some embodiments, functionalized powder particles with hydrophilic surfaces may adsorb the hydrophilic heads of membrane lipids, resulting in the membrane spreading over the nanostructure surface. As the membrane spreads more, it may strain to the point of failure, causing cell death. For both examples, the physical cause of cell death may not be related to cell membrane penetration by any nanostructure. In some examples, the hydrophobicity or hydrophilicity may be altered or amplified by further functionalizing the particles with compounds.

[0085] In some examples, the cell killing rate (cells killed per time) or cell lysis rate (cells lysed per time) can be increased by subjecting the antimicrobial functionalized powder particles to a mechanical process. Any mechanical process can be selected such that it imposes additional forces on the cells, resulting in an increase in the attractive forces between the functionalized powder and the cell membrane, which can then cause cell membrane rupture. For example, one or more functionalized particles can be subjected to mechanical vibration to rupture the cells. In some embodiments, one or more functionalized particles can be subjected to mechanical deformation to rupture the cells. In some examples, the mechanical deformation of the functionalized powder particles can be achieved by thermal cycling deformation, or piezoelectric deformation.

[0086] Chemical mode of action: In some examples, one or more functionalized powder particles may be subjected to one or more additional processes that add active antimicrobial chemical moieties. Such surface functionalization may be aided by an increase in surface area of ​​the functionalized particles compared to non-functionalized particles, wafers, or substrates. For example, one or more functionalized particles decorated with Ag or Cu nanoparticles may comprise a composite with antimicrobial properties. In some examples, the metal nanoparticles may remain as residuals from the MACE process. In some examples, the active antimicrobial chemical moieties may be added to the functionalized particles. In some embodiments, the active chemical moieties may be added to structurally functionalized particles that do not have antimicrobial properties. In some embodiments, the functionalized particles may be used as a vehicle to incorporate chemical moieties into the composite.

[0087] Other Physical Modes of Action: In some examples, one or more functional powder particles may be antimicrobial if their chemical composition and crystal structure allow for the emission of ultraviolet (UV) light. The UV light emission may be facilitated by the application of an electric field or other methods. For example, the functional particles may include InGaN, a UV-emitting semiconductor material. In some embodiments, InGaN, diamond carbon, BN, AlN, AlGaN, or AlGaInN may be selected as the UV-emitting material for the antimicrobial functional powder particles.

[0088] In some examples, the functionalized powder particles may have enhanced antimicrobial properties in the presence of microwave radiation. Microwave radiation of sufficient intensity may kill cells. At lower intensities, microwave radiation may significantly damage cells. Microwave radiation may kill cells in the presence of one or more antimicrobial functionalized particles as a result of two or more cell damage mechanisms acting in concert. Such embodiments may reduce the intensity of microwave radiation required to kill cells.

[0089] In some examples, one or more functional powder particles may be designed for efficient light absorption, thereby enhancing the antimicrobial properties of the material. Efficient light absorbers can convert light energy into heat, which can cause cell damage or cell death of cells in contact with the material. In some examples, one or more functional powder particles may be designed for efficient infrared radiation, thereby enhancing the antimicrobial properties of the material. Irradiation of cells via infrared radiation can promote sufficient warming to damage or kill microorganisms. For example, GaAs particles may be selected as the particles to be functionalized due to the enhanced infrared (IR) emission spectrum for the material. In some embodiments, AlGaAs may be selected as the infrared emitting semiconductor particles.

[0090] In some examples, the functionalized powder particles may be selected such that the surface of the functionalized powder particles prevents cell adhesion, and such a surface may inhibit or prevent the growth and replication of cells in contact with the composite surface.

[0091] Other Example Applications Hydrophobic and Hydrophilic Surfaces: One or more functional particles described herein may be incorporated into the surface of an article to alter the hydrophobicity or hydrophilicity of the surface. The surface energy, surface chemistry, nano- and micro-structure of the functional particles each affect the interaction between water and the macro-surface. Appropriate functional particles may be selected for a given application. For example, FIG. 27 shows an example of DI-H2O contact angle measurements on functionalized ABS plastic substrates. Samples 1, 2, 3, and 4 were structurally functionalized, resulting in a hydrophobic surface coating, while Sample 5 contains non-functionalized particles, resulting in a hydrophilic surface coating. The change in surface energy can be seen by comparing the contact angles of Samples 1, 2, 3, and 5, which all have the same Si chemical composition and crystal structure, but the structural functionalization of Samples 1, 2, and 3 results in a larger contact angle. Chemical functionalization of the structurally functionalized particles may increase the hydrophobicity or antifouling properties of the coating.

[0092] Anti-reflective surfaces: One or more functional powder particles may be designed to create anti-reflective surfaces. A significant amount of light is generally reflected at the steep surface / air interface of a given surface due to the difference in refractive index between the material and air. Functional particles may be designed with multi-directional micro- and nano-structures to enhance the wide-angle anti-reflective properties of the material. Figure 37 shows examples of specular reflectance spectra at an incidence angle of 45° (190-900 nm wavelength) from ABS plastic substrates coated via the method described in Example 16 with powders functionalized via the method described in Example 2 (Sample E), Example 11 (Sample D), and Example 13 (Sample C). An ABS plastic substrate coated via the method described in Example 16 with non-functionalized Si particles (Sample F), a bare ABS substrate, and a polished Si wafer are shown as references. The average reflectance of sample E shown in Figure 37 is 0.026% for light between 190-900 nm, 0.029% for light between 190-380 nm, 0.021% for light between 380-740 nm, and 0.033% for light between 740-900 nm. The average reflectance of sample D shown in Figure 37 is 0.035% for light between 190-900 nm, 0.046% for light between 190-380 nm, 0.024% for light between 380-740 nm, and 0.045% for light between 740-900 nm. The average reflectance of sample C shown in Figure 37 is 0.077% for light between 190-900 nm, 0.13% for light between 190-380 nm, 0.055% for light between 380-740 nm, and 0.062% for light between 740-900 nm. The average reflectance of Sample F shown in FIG. 37 is 0.085% for light between 380-900 nm, 0.081% between 380-740 nm, and 0.095% between 740-900 nm. The reduction in reflectance between surfaces containing non-functional Si powder particles (Sample F) and surfaces containing functional particles (Samples C, D, and E) is significant over a wide range of wavelengths. For example, the average reflectance of Sample F between 380-740 nm is also approximately four times that of Sample E. As seen in FIG. 2, the heterofunctional particle morphology of Product E, including pits and pores, aids in the broad wavelength anti-reflection properties.Furthermore, these functional particle-surface complexes provide anti-reflection over a wide range of angles due to their nano- and micro-scale morphology.

[0093] Light-absorbing surface: One or more functional powder particles may be designed to create a light-absorbing surface. One or more functional particles described herein may be embedded in a surface to form a material density gradient, resulting in a refractive index gradient that smoothly transitions between air and bulk material. Such a gradient may be a broadband light absorber. In some embodiments, the antireflective material may have enhanced light-absorbing properties due to multiple light scattering events that increase the number of interactions between photons and the functional powder particles. In some embodiments, a combination of heterofunctional morphologies may aid in broadband light absorption. For example, as seen in the broadband antireflective properties of Sample E shown in FIG. 37, which includes heterofunctional particles with a surface that includes pits and pores, as seen in FIG. 2.

[0094] Fibers: For example, as depicted in FIG. 10, one or more functional powder particles may be embedded in synthetic or natural fibers. Such fibers may be used in textiles, composites, or other materials. The functional powders may be selected to impart various properties onto the fibers. Such applications may cause the fibers to have properties including, but not limited to, antibacterial, hydrophobic, hydrophilic, antireflective, light absorbing, antistatic, and improved durability.

[0095] Piezoelectric devices: One or more functionalized powder particles may include piezoelectric devices, for example as shown in FIG. 11. In some examples, functionalized semiconductor powder particles are embedded in an insulating material and are in physical contact with a conductive material on either side of the insulator. Application of an electric field across the device may result in a mechanical change in the functionalized powder particles. Optionally, the device may allow sensing of mechanical forces acting on the particle or the device by changes in the electric field across the device. Optionally, structural functionalization of the particle may change the lattice structure of the particle and therefore its band structure, and may aid in harnessing its piezoelectric properties.

[0096] Antistatic applications: One or more functional powder particles may be used to reduce charge buildup. One or more functional particles embedded in a medium may reduce the overall resistance of the composite due to the electronic properties of the selected semiconductor. For example, one or more functional powder particles may be embedded in a plastic to reduce the buildup of charge in the plastic. Materials made antistatic by the incorporation of functional powder particles may be more resistant to dust buildup and less likely to cause electric shock. Optionally, one or more functional powder particles may be affixed to the surface of a product and then modified, coated, or plated with a conductive material. Micro- and nano-scale structures will increase the capacitance per contact area. Micro- and nano-scale shapes and protruding structures may increase discharge from the surface. Figure 5(d) shows a cross-sectional SEM image of a Pt-coated rock pillar structure.

[0097] Isolated nanostructures: Prepared nanostructures can be harvested from the surface of one or more functional powder particles by mechanical separation or other methods. In some instances, isolated nanostructures can be dispersed in bulk media when the nanoscale properties of semiconductors or insulators are more desirable than the properties of functional powder particles with a broader range of nanoscale and microscale physical behavior. In some instances, layer-by-layer growth methods can be used to form an interface between one or more functional powder particles and another medium having nanostructures embedded on its surface. In such instances, the powder particle cores can be separated from the nanostructures, leaving behind a medium having semiconductor or insulator nanoparticles embedded on its surface. The embedded nanostructures can be used as catalysts to grow other structures on the surface of the medium.

[0098] Photovoltaic devices: One or more functional powder particles may be applied as an additive or component in photovoltaic devices. For example, one or more p-type functional powder particles may be coated with an n-type semiconductor to create a material for application in photovoltaic devices. The size and shape of the functional powder particle nanostructure may change its band structure or band gap, which may be due to quantum confinement. Thus, the design of the functional powder particle may allow the band gap to be changed to be optimal for the photovoltaic device. The nanostructures on the particle surface may increase light absorption due to the increase in light scattering events and refractive index gradients formed by the nanostructures and microstructures on the powder surface. The functional powder particles may absorb light over a larger bandwidth and at a larger range of angles depending on the morphology and structure of their surface. The increase in efficiency of light absorption is not limited to any particular nanostructure only, but may also be caused by some variants of the functional powder particles.

[0099] Light detection devices: In some examples, one or more functionalized powder particles may be used as additives or components of light detection devices. Nanostructures on the particle surface may increase light absorption due to light scattering events and increased refractive index gradients formed by nanostructures and microstructures on the powder surface. Functionalized powder particles may absorb light over a larger bandwidth and at a larger range of angles due to their surface texture and structure. The increase in efficiency of light absorption is not limited to any particular nanostructures only, but may also be caused by some variants of functionalized powder particles.

[0100] Light-emitting devices: In some examples, one or more functional powder particles may be used as an additive or component of a light-emitting device. For example, a light-emitting diode (LED) device may include one or more particles of a functional powder. Light extraction is an important aspect of LED efficiency, since a large difference in reflectance between the emitting material and air can result in high internal reflection. Nanostructures on the surface of the functional powder particles can provide a refractive index gradient due to the material density gradient at the particle surface, reducing the amount of internal reflection between the LED material and the air interface. For example, porous pyramidal structures on the powder surface would provide a material density gradient. A wide range of surface nanostructures and microstructures may be used for LED applications and are not limited to the aforementioned structures.

[0101] Non-Limiting Examples: One or more functional particles of the present disclosure can be incorporated into many products, such as keyboards, computers, computer peripherals, computer mice, pressure sensitive adhesive backed films, containers, bottles, appliances, cookware, kitchen utensils, curtains, beverage dispensers, shopping carts, hydration packs, bladders, valves, tubing, and bags, fluid pipes, sewer pipes, gas pipes, footwear, telephones and peripherals, video game consoles and controllers, manned and unmanned vehicles, tires, buttons, holes, handrails, trains, awnings, cutting boards, drying racks, fluid tanks, drains, tubing, filters, traps, nets, underwater vehicles, ships, and amphibious vehicles, refrigerators, freezers, fingerprint readers, and palm print readers. state readers and scanners, propellers, humidifiers, dehumidifiers, shower mats, exercise, gym, and yoga mats, athletics equipment, liquid dispensers, handles and knobs, automated teller machines, credit cards and other plastic cards, waste bins, pet bowls, pet carriers, mass transit equipment, electronic equipment, tiles, showers, toilets, trash and recyclable containers, rails, floors, ceilings, walls, seat covers, tables, counters, chairs, cabinets, switches and switch panels, food preparation tables, food wrap, hair styling tools and fixtures such as combs, brushes, razors, and scissors, sinks, faucets, basins, bench tops, shelves, processing and packaging equipment and machinery, food and beverage processing and manufacturing equipment, meat processors, clothing, eyewear, bags, jetties, piers, wharves, and pontoon pillarspillars), marine and water equipment, marine and water pipes and cables, oil and gas equipment, aircraft, military vehicles, military supplies and gear, siding, building materials, concrete, textiles / fabrics, firearms, paints, surface coatings, wetsuits, water equipment, lighting, solar panels, HVAC, telescopes, cameras and lenses, optical devices, photodetectors, tools, masks, grips, watches, coolers, transceiver radios, lockers, storage bins, bins, packaging, squeegees, scaffolding, currency, musical instruments and equipment, sewing tools, fishing equipment, jewelry, knives, locks, washers and dryers, ovens, dishwashers, stoves, televisions, carpets, rugs and coverings, rug mats, combat gear, pens, pencils and other writing implements, office supplies, furniture, artwork, roofing, automobiles, medical equipment and procedures, dental equipment and devices, bandages, cribs, pacifiers, Including, but not limited to, trays, toys, baby bottles and accessories, thermometers, changing tables and covers, high chairs, breast pumps, fuel pumps, charging stations, cords, bicycles, motorcycles, remote controls, mattresses, pools and accessories, walkers / canes, school supplies, playground equipment, cafeteria equipment, hoses, tents, flies and tarps, umbrellas, drains, grills, smokers, smoking equipment, rubber products, plastic products, braces, speakers, condoms, toothbrush holders, sponges, towels, pumps, ropes, bioanalyzers, biomaterial extraction / harvesting equipment, gloves, building components, office supplies, packaging, conveyor belts, manufacturing equipment, scooters, drones, cases, metal products, glass products, ceramic products, books, restaurant menus, paper and paper products, electrical cables, dining mats, protective covers, and signs. The article may be selected from office consumables, office supplies, electronics, containers, kitchen utensils, cookware, household goods, textiles, hardware, consumer goods, vehicles and marine, filters, pumps, water fixtures, surfaces, furniture, fixtures, equipment, building materials, military equipment, tools, solar cells, currency, medical supplies, medical devices, paper products, manufacturing equipment, food processing equipment, and optical instruments. Optionally, the article comprises rubber, plastic, metal, glass, or ceramic.

[0102] How to create a composite product Conventional techniques may be used to coat a product with one or more functional particles of the present disclosure. For example, adhesives, binders, or similar materials may be used to attach at least one functional particle to the product. The functional powder particles may be fully exposed, partially exposed, or fully embedded in an adhesive medium on the product surface.

[0103] Methods of embedding functional particles in thermoplastics: One or more functional powder particles may be added to the thermoplastic. In some examples, one or more heated functional powder particles may be added to the surface of the heated thermoplastic. The elevated temperature of the thermoplastic and the functional particles allows the thermoplastic to adsorb onto the particle surface. Optionally, the thermoplastic may include the functional powder particles in the bulk. The thermoplastic may be solidified such that the particles are partially adsorbed or fully absorbed into the plastic medium. Optionally, a plastic solution may be used to temporarily liquefy or melt the plastic. Optionally, powder coating, electrostatic painting, or a roll-to-roll method may be used to add the functional particles to the thermoplastic. The method of adding the functional particles to the thermoplastic is not limited to the above-mentioned methods.

[0104] Methods for embedding functional particles in molded materials: In some examples, one or more functional powder particles are temporarily fixed to the interior surface of a mold or template. The mold or template is filled with a liquid or flexible material, including glass, ceramic, concrete, elastomer, or metal. The molded or templated material is allowed to solidify, and the mold or template is removed. In some examples, the molded or templated material will retain one or more functional powder particles embedded on the material surface. Optionally, the molded or templated material may not retain the particles, but will retain surface nanostructured impressions of one or more functional powder particles. In other examples, the molded or templated material will retain the nanostructured portion of one or more functional powder particles, while the original mold or template will retain the bulk portion of the powder particles. EXAMPLES

[0105] Example 1: 10.0 g of crystalline Si powder with a purity of 99.995% and a particle size range of 10 μm-150 μm and an average particle size of 28 μm is suspended in a bath of acetone by stirring for 10 minutes. The acetone bath is then sonicated for 10 minutes. The acetone / Si powder mixture is filtered and the Si powder is transferred to a bath of methanol. The crystalline Si powder is suspended in a bath of methanol by stirring for 10 minutes. The methanol bath is then sonicated for 10 minutes. The methanol / Si powder mixture is filtered and rinsed with DI-H2O. The powder is transferred and suspended in a solution of DI-H2O and 1.5M HF by stirring for 5 minutes to remove native oxides. The powder is then filtered and rinsed with DI-H2O. The Si powder is then subjected to metal-assisted chemical etching (MACE). The Si powder is suspended in a solution of 0.15 M HF, 0.035 M AgNO3, and DI-H2O with stirring for 8 minutes to deposit Ag nanoparticles on the surface of the powder particles. The powder is then filtered and transferred to a solution of 5.5 M HF, 2 M H2O2, and DI-H2O and suspended with stirring for 30 minutes at an initial bath temperature of 25°C. The reaction is exothermic, so the bath temperature may increase, accelerating the etching rate. After the MACE process, the Si powder is filtered and then thoroughly rinsed with DI-H2O, and then may be blown with nitrogen gas to remove residual moisture. The resulting material is a Si powder with a nanostructured surface.

[0106] Example 2: Functionalized Si powder is prepared by the method described in Example 1. The functionalized Si particles are then exposed to a bath of 7M HNO3 and DI-H2O for 5 minutes to remove Ag from the Si particles and collected. The Si powder may be given a final rinse with DI-H2O and then blasted with nitrogen gas to remove residual moisture. The resulting material is a Si powder with a nanostructured surface. The collected metal may be recycled for further use.

[0107] Example 3: 10.0 g of crystalline Si powder with a purity of 99.995% and a particle size range of 10 μm-150 μm and an average particle size of 28 μm is suspended in a bath of acetone by stirring for 10 minutes. The acetone bath is then sonicated for 10 minutes. The acetone / Si powder mixture is filtered and the Si powder is transferred to a bath of methanol. The crystalline Si powder is suspended in a bath of methanol by stirring for 10 minutes. The methanol bath is then sonicated for 10 minutes. The methanol / Si powder mixture is filtered and rinsed with DI-H2O. The powder is transferred and suspended in a solution of DI-H2O and 1.5M HF by stirring for 5 minutes to remove native oxides. The powder is then filtered and rinsed with DI-H2O. The Si powder is then subjected to MACE. The Si powder is suspended in a solution of 0.15 M HF, 0.035 M AgNO3, and DI-H2O with stirring for 8 minutes to deposit Ag nanoparticles on the surface of the powder particles. The powder is then filtered and transferred to a solution of 5.5 M HF, 2 M H2O2, and DI-H2O and suspended with stirring for 25 minutes at an initial bath temperature of 25°C. The reaction is exothermic, so the bath temperature may increase, accelerating the etch rate. After the MACE process, the Si powder is filtered and then thoroughly rinsed with DI-H2O.

[0108] The Si powder is then subjected to another round of MACE. The Si powder is suspended in a solution of 0.15 M HF, 0.035 M AgNO3, and DI-H2O with stirring for 0.5 min to deposit additional Ag nanoparticles on the surface of the powder particles. The powder is then filtered and transferred to a solution of 5.5 M HF, 2 M H2O2, and DI-H2O and suspended with stirring for 15 min at an initial bath temperature of 25°C. The reaction is exothermic, so the bath temperature may be increased to accelerate the etch rate. After MACE, the Si powder may be given a final rinse with DI-H2O and then blown with nitrogen gas to remove residual moisture. The resulting material is a Si powder with a nanostructured surface.

[0109] Example 4: Functionalized Si powder is prepared by the method described in Example 3. The functionalized Si particles are then exposed to a bath of 7.85 M HNO3 and DI-H2O for 5 min to remove the Ag from the Si particles and collected. The Si powder is given a final rinse with DI-H2O and then placed in a vacuum chamber to remove residual moisture. The resulting material is a Si powder with a nanostructured surface. The collected metal may be recycled for further use.

[0110] Example 5: Crystalline Si powder with particle size range 10μm-200μm is suspended in a bath of acetone by stirring for 10 minutes. The acetone bath is then sonicated for 10 minutes. The acetone / Si powder mixture is filtered and the Si powder is then transferred to a methanol bath. Crystalline Si powder is suspended in a bath of methanol by stirring for 10 minutes. The methanol bath is then sonicated for 10 minutes. The methanol / Si powder mixture is filtered and the powder is then transferred to a vacuum oven heated at 80°C for at least 1 hour. The Si powder is then subjected to chemical etching (CE). The Si powder is stirred in a solution of 1.0M KOH and DI-H2O for 20 minutes at an initial bath temperature of 50°C. The reaction is exothermic, so the bath temperature may increase, accelerating the etching rate. The resulting powder morphology and the etching rate depend on the bath temperature, duration, and agitation. Agitating the solution reduces the temperature gradient in the bath, resulting in more uniform functionalization among particles. Optionally, a static bath may result in non-uniformly functionalized particles among particles, which may be advantageous for creating a dispersion of structurally functionalized particles in a single batch. After the CE process, the Si powder is filtered and thoroughly rinsed with deionized water.

[0111] The Si powder is then subjected to MACE. The Si powder is suspended in a solution of 0.20 M HF, 0.05 M AgNO3, and DI-H2O with stirring for 5 minutes to deposit Ag nanoparticles on the surface of the powder particles. The powder is then filtered and transferred to a solution of 5.5 M HF, 2 M H2O2, and DI-H2O and suspended with stirring for 30 minutes at an initial bath temperature of 25°C. This reaction is exothermic, so the bath temperature may increase, accelerating the etching rate. After the MACE process, the Si powder is filtered and then thoroughly rinsed with DI-H2O. The Si particles are then exposed to a bath of 7.85 M HNO3 and DI-H2O for 5 minutes to remove the Ag from the Si particles and collect them. The Si powder is given a final rinse with DI-H2O and then placed in a vacuum chamber to remove residual moisture. The resulting material is a Si powder with a nanostructured surface.

[0112] Example 6: 10.0 g of crystalline Si powder with a purity of 99.995% and an average particle size of the particle size range 10 μm-150 μm and 28 μm is sonicated and suspended in a bath of acetone and then methanol by stirring for 15 minutes each to remove organic contaminants. The washed Si powder is filtered and rinsed with DI-H2O. The powder is transferred to a filter reactor and suspended in a solution of DI-H2O and 1.35 M HF by stirring at 400 rpm for 5 minutes to remove native oxides. The solution is then removed from the reactor. The Si powder is then subjected to MACE. The Si powder is suspended in a solution of 0.15 M HF, 0.035 M AgNO3, and DI-H2O by stirring at 400 rpm to deposit Ag nanoparticles on the surface of the powder particles. The solution is then removed from the reactor after 8 minutes. The powder is then etched with a static etching solution containing 48% w / w HF, 30% w / w H2O2, and DI-H2O (1:1:3 v / v), initially at 25 °C. H2O2 is added continuously for the first 10 min. Etch duration, chemical concentration, temperature, and H2O2 addition rate are varied depending on the intended resulting nanostructured Si powder. The etching solution is removed from the reactor, and the powder is then rinsed with DI-H2O or ethanol. Optionally, the powder is exposed to a bath of 7.85 M HNO3 and DI-H2O for 5 min to remove the Ag from the functionalized particles and recover. The recovered metal may be recycled for further use. The powder is given a final rinse with DI-H2O or ethanol, and then placed in an oven or vacuum chamber at 50 °C to remove residual moisture. Figure 4 shows an example of the resulting nanowire surface formed after 60 min of etching.

[0113] Example 7: 10.0 g of crystalline Si powder with a purity of 99.995% and an average particle size range of 10 μm-150 μm and 28 μm is sonicated and suspended in a bath of acetone and then in a bath of methanol by stirring for 15 minutes each to remove organic contaminants. The washed Si powder is filtered and rinsed with DI-H2O. The powder is transferred to a filter reactor and suspended in a solution of DI-H2O and 1.35 M HF by stirring at 400 rpm for 5 minutes to remove native oxides. The solution is then removed from the reactor. The Si powder is then subjected to MACE. The Si powder is suspended in a solution of 0.15 M HF, 0.035 M AgNO3, and DI-H2O by stirring at 400 rpm to deposit Ag nanoparticles on the surface of the powder particles. The solution is then removed from the reactor after 8 minutes. The powder is then suspended in the etching solution, initially at 25° C., by stirring at 250 rpm. The powder-containing solution is agitated to prevent films or bubbles or crusts from forming at the solution / air interface. Films, bubbles, or crusts may result in heterofunctional particles between the particles. The etching solution contains 48% w / w HF, 30% w / w H2O2, and DI-H2O (1:1:3 v / v), and H2O2 is added continuously for the first 10 min. Etch duration, chemical concentrations, temperature, agitation rate, and H2O2 addition rate may be varied depending on the nanostructured Si powder that is intended to result. Figures 17, 16, and 5c and 5d show examples of the resulting nanostructured surfaces at etching durations of 30, 60, and 90 min, respectively. The etching solution is removed from the reactor, and the powder is then rinsed with DI-H2O or ethanol. Optionally, the powder is suspended in a solution of 7.85 M HNO3 and DI-H2O with stirring at 250 rpm for 5 minutes to dislodge and recover the Ag from the functionalized particles. The solution is removed from the reactor and the powder is then given a final rinse with DI-H2O or ethanol.

[0114] The movement of the etching solution has a significant effect on the resulting nanostructures. For example, the nanostructures shown in Figures 4 and 16 were produced from the procedures described in Example 6 and above (Example 7). The etching conditions and etching durations are identical except that the etching solution is not stirred (Example 6) and is stirred (Example 7). However, Figure 4 shows a morphology that includes nanowires, while Figure 16 shows a morphology that includes coral structures. Furthermore, the resulting etch depth (the distance between the surface and the outer edge of the unetched solid particulate core) is 10 times deeper when the etching solution is static than when the etching solution is stirred at 250 rpm for the same duration, as seen in Figure 32. As a result, the etch depth rate (etch depth / time) is about 10 times greater when the etching solution is static than when it is stirred at 250 rpm. When static, the Ag nanoparticles move along a relatively straight path from the surface of the Si particles toward the particle core, thereby forming the high aspect ratio nanowires shown in Figure 4. On the other hand, the stirring and movement during etching may introduce additional forces on the Ag nanoparticles during their transfer to the Si particles, thereby altering the transfer and the resulting etched structure. As confirmed in Figure 16, the stirring may result in an irregular coal structure with a low aspect ratio.

[0115] The nanowire structures formed via the method described in Example 6 are structurally more delicate than those formed via the method described in Example 7. For example, stirring the particles separately in solution at 250 rpm for 5 minutes resulted in significant damage and loss of nanowires from the particles of Example 6. On the other hand, the interconnected structures found on the particles of Example 7 did not show significant degradation from being stirred in solution or by normal handling. Furthermore, FIG. 4 shows a particle that was not subjected to additional stirring, but a section of the particle surface is free of nanowires (functional structures) that were destroyed by normal handling. The interconnected structural features found in structures such as, but not limited to, rock pillars and corals provide mechanical durability.

[0116] Figure 25 shows X-ray diffraction data from functionalized powder particles after 90 minutes of etching, as well as non-functionalized Si particles for comparison. A shift in peak position can be seen for the Si(111) and Si(311) peaks of the functionalized powder, which indicates that <111> 0.194% lattice elongation along the direction, and <311> direction, whereas the positions of the Si(220), Si(400), and Si(331) peaks remain unchanged. The X-ray data suggest that the crystalline unit cells are anisotropic, being distorted by the structural functionalization of the particles.

[0117] Example 8: Functionalized Si powder is prepared by the method described in Example 7 with an etching duration of 90 min. The powder is added to H2SO4 and H2O2 (4:1 v / v) for 25 min to remove organic residues and prepare silanol groups on the surface. The powder is filtered and thoroughly rinsed with DI-H2O, then dried at 75 degrees for 30 min. The powder is added to a 2.5 mM octadecyltrichlorosilane solution prepared in toluene and allowed to react for 120 min. The chemically functionalized powder is then removed from the solution by filtration and rinsed with chloroform. Figure 28 shows the attenuated total reflectance Fourier transform infrared spectra (ATR-FTIR) of chemically and structurally functionalized Si powder (Sample D), structurally functionalized Si powder (Sample C), chemically functionalized Si powder (Sample B), and non-functionalized Si powder (Sample A). Based on the peak positions of the symmetric and asymmetric CH stretches, both the two chemically functionalized powders (samples B and D) show well-ordered monolayer formation. However, at least three-fold increased absorbance is seen in the structurally and chemically functionalized powder (sample D), corresponding to a higher number of functional molecules per particle as a result of the larger surface area of ​​the structurally functionalized particles. Furthermore, the results show that the structurally functionalized particles (samples C and D) have at least three times the surface area of ​​the unfunctionalized Si particles (samples A and B). Chemical functionalization may further increase the hydrophobicity of the structurally functionalized particles. Typically, structurally functionalized particles allow a larger amount of chemical functionalization due to their larger surface area than unfunctionalized particles.

[0118] Example 9: 10.0 g of crystalline Si powder with a purity of 99.995% and an average particle size of the particle size range 10 μm-150 μm and 45 μm is sonicated and suspended in a bath of acetone and then methanol with stirring for 15 minutes each to remove organic contaminants. The washed Si powder is filtered and rinsed with DI-H2O. The powder is transferred to a filter reactor and suspended in a solution of DI-H2O and 1.35 M HF with stirring at 400 rpm for 5 minutes to remove the native oxide. The solution is then removed from the reactor. The Si powder is then subjected to a one-step MACE. The Si powder is suspended in a solution of 4.6 M HF, 0.55 M H2O2, 0.035 M Cu(NO3)2·2.5H2O, and DI-H2O with stirring at 250 rpm to deposit Cu nanoparticles on the surface of the powder particles and etch the particles. The solution is initially at 25°C. Etching duration, chemical concentration, temperature, and stirring speed may be varied depending on the intended resulting nanostructured Si powder. Figures 20(a) and 20(b) show examples of the resulting nanostructured surfaces at etching durations of 30 and 10 minutes, respectively. The etching solution is removed from the reactor, and the powder is then rinsed with DI-H2O or ethanol. Optionally, the powder is suspended in a solution of 7.85 M HNO3 and DI-H2O by stirring at 250 rpm for 5 minutes to remove and recover the Cu from the functionalized particles. The recovered metal may be recycled for further use. The solution is removed from the reactor, and the powder is then given a final rinse with DI-H2O or ethanol.

[0119] Example 10: 10.0 g of crystalline Si powder with a purity of 99.995% and an average particle size in the particle size range of 10 μm-150 μm and 45 μm is sonicated and suspended in a bath of acetone and then in a bath of methanol by stirring for 15 minutes each to remove organic contaminants. The washed Si powder is filtered and rinsed with DI-H2O. The powder is then suspended in an etching solution, initially at 25° C., by stirring at 250 rpm. The powder-containing solution is agitated to prevent a film or bubble or crust from forming at the solution / air interface. The etching solution consists of 6.7 M KOH and DI-H2O. The temperature of the solution increases during the reaction, and after 9 minutes, the temperature measured by an IR thermometer at the top surface of the solution was 55° C. The etching duration, chemical concentration, and solution temperature may be varied depending on the nanostructured Si powder intended to result. FIG. 21 shows an example of a resulting nanostructured surface produced after 9 minutes. The etching solution is removed from the reactor and the powder is then rinsed with DI-H2O or ethanol.

[0120] Example 11: 10.0 g of crystalline Si powder with a purity of 99.995% and a particle size range of 75-150 μm is sonicated and suspended in a bath of acetone and then in a bath of methanol with stirring for 15 min each to remove organic contaminants. The washed Si powder is filtered and rinsed with DI-H2O. The powder is then suspended in an etching solution with stirring at 250 rpm. The etching solution consists of 5% (w / w) NaOH and DI-H2O, initially at 60°C. The temperature measured by an IR thermometer at the top of the solution increases to a maximum of 71°C in the first 5 min, then decreases to a final temperature of 33°C in the next 55 min. The etching duration, chemical concentration, and solution temperature may be varied depending on the Si powder of the structure intended to result. Figure 22 shows an example of a resulting nanostructured surface produced after 15 min. Particles are removed by filtration and the powder is rinsed with DI-H2O or ethanol.

[0121] Example 12: 10.0 g of crystalline Si powder with a purity of 99.995% and a particle size range of 75-150 μm is sonicated and suspended in a bath of acetone and then in a bath of methanol by stirring for 15 minutes each to remove organic contaminants. The washed Si powder is filtered and rinsed with DI-H2O. The powder is then suspended in the etching solution by stirring at 250 rpm. The powder-containing solution is agitated to prevent a film or bubble or crust from forming at the solution / air interface. The etching solution consists of 1% (w / w) KOH and DI-H2O, initially at 60° C. and then without heating. The etching duration, chemical concentration, and solution temperature may vary depending on the Si powder of the structure intended to result. The solution is removed from the reactor after 70 minutes and the powder is washed with DI-H2O and then removed from the reactor. The Si powder is then subjected to MACE. The functionalized Si powder is suspended in a solution of 0.15 M HF, 0.035 M AgNO3, and DI-H2O by stirring at 400 rpm to deposit Ag nanoparticles on the surface of the functionalized powder particles. The solution is then removed from the reactor after 8 minutes. The powder is then suspended in an etching solution, initially at 25°C, by stirring at 250 rpm. The reaction is exothermic, and the peak temperature measured by an IR thermometer at the top of the solution is 85°C at 5 minutes. The powder-containing solution is stirred to prevent a film or bubble or crust from forming at the solution / air interface. The etching solution contains 48% w / w HF, 30% w / w H2O2, and DI-H2O (1:1:3 v / v), and H2O2 is added continuously for the first 9 minutes. The etching duration, chemical concentrations, solution temperature, and stirring speed may be varied depending on the micro- and nanostructured Si powders that are intended to result. Figure 23 shows an example of the resulting heterofunctionalized surface produced after 15 minutes. The solution is removed from the reactor and the powder is rinsed with DI-H2O or ethanol.Optionally, the powder is suspended in a solution of 7.85 M HNO3 and DI-H2O by stirring at 250 rpm for 5 minutes to dislodge and recover Ag from the functionalized particles. The recovered metal may be recycled for further use. The solution is removed from the reactor, and the powder is then given a final rinse with DI-H2O or ethanol.

[0122] Example 13: 10.0 g of 99% pure amorphous SiO powder with particle size range 38-45 μm is transferred to a filtration reactor. The SiO powder is then subjected to MACE. The SiO powder is suspended in a solution of 0.15 M HF, 0.035 M AgNO3, and DI-H2O by stirring at 400 rpm to deposit Ag nanoparticles on the surface of the powder particles. The solution is then removed from the reactor after 8 minutes. The powder is then suspended in an etching solution, initially at 25° C., by stirring at 250 rpm. The reaction is exothermic, and the peak temperature measured by an IR thermometer at the top surface of the solution is 83° C. at 2 minutes. The powder-containing solution is agitated to prevent a film or bubble or crust from forming at the solution / air interface. The etching solution contains 48% w / w HF, 30% w / w H2O2, and DI-H2O (1:1:3 v / v), and H2O2 is added continuously for the first 7.5 min. Etch duration, chemical concentrations, solution temperature, and stirring speed may vary depending on the nanostructured SiO powder intended to result. Figure 33 shows an example of a resulting nanostructured surface for an etching duration of 60 min. The etching solution is removed from the reactor, and the powder is then rinsed with DI-H2O or ethanol. Optionally, the powder is suspended in a solution of 7.85 M HNO3 and DI-H2O by stirring at 250 rpm for 5 min to remove and recover Ag from the functionalized particles. The recovered metal may be recycled for further use. The solution is removed from the reactor, and the powder is then given a final rinse with DI-H2O or ethanol.

[0123] Example 14: 3.0 g of crystalline Si powder, 99% pure, consisting of α- and β-phases, with average particles of 40 μm in size, as shown by X-ray diffraction in FIG. 26, is transferred to a reactor containing 48% w / w HF and HNO3 (3:1 v / v), initially heated to 80° C. and maintained at 75-100° C. The powder is then suspended in the etching solution by stirring at 241 rpm. The powder-containing solution is agitated to prevent a film or bubble or crust from forming at the solution / air interface. Etching duration, chemical concentration, solution temperature, and agitation speed may vary depending on the intended resulting nanostructured SiC powder. FIG. 24 shows an example of the resulting nanostructured surface at 150 min of etching. Particles are removed by filtration, and the powder is rinsed with DI-H2O or ethanol.

[0124] Example 15: 3.3 g of crystalline Ge powder with a purity of 99.999% and a particle size of less than 150 μm is transferred to a reactor and suspended in a solution of DI-H2O and 1.35 M HF by stirring at 400 rpm for 5 minutes to remove the native oxide. The solution is then removed from the reactor. The Ge powder is then subjected to MACE. The Ge powder is suspended in a solution of 0.14 M HF, 0.035 M AgNO3, and DI-H2O by stirring at 400 rpm to deposit Ag nanoparticles on the surface of the powder particles. The solution is then removed from the reactor after 8 minutes. The powder is then suspended in an etching solution, initially at 25° C., by stirring at 250 rpm. The reaction is exothermic and the temperature measured by an IR thermometer at the top of the solution is 55° C. in 12 minutes. The powder-containing solution is stirred to prevent a film or bubble or crust from forming at the solution / air interface. The etching solution contains 48% w / w HF, 30% w / w H2O2, and DI-H2O (1:1:3 v / v), and H2O2 is added continuously for the first 6 minutes. The etching duration, chemical concentrations, solution temperature, and stirring speed may be varied depending on the resulting intended nanostructured Ge powder. Figures 35 and 36 show the functionalized surface resulting from an etching duration of 5 minutes. The etching solution is removed from the reactor, and the powder is then rinsed with DI-H2O or ethanol. Optionally, the powder is suspended in a solution of 7.85 M HNO3 and DI-H2O by stirring at 250 rpm for 5 minutes to remove and recover Ag from the functionalized particles. The recovered metal may be recycled for further use. The solution is removed from the reactor and the powder is then given a final rinse with DI-H2O or ethanol.

[0125] Example 16: A functional powder is prepared via the method described in Examples 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15. The functional powder is applied to the plastic by temporarily liquefying the plastic with a chemical solvent. Examples of plastic solvents include, but are not limited to, dichloromethane, benzene, toluene, n-hexane, hexane, petroleum ether, acetalaldehyde, methanol, analine, carbon tetrachloride, cyclohexane, diethyl ether, xylene, methyl ethyl ketone, methyl acetate, trichloroethylene, and methyl methacrylate monomer. The solvent and functional powder may be applied to the plastic in any order or simultaneously. The solvent is then evaporated and the plastic is solidified. As illustrated in Figures 9(b) and 9(c), the resulting composite consists of functional powder attached to the plastic surface and / or within the bulk and can have complex shapes or geometries (in contrast, a structurally functionalized rigid wafer would not be able to accommodate complex surface geometries). The functional powder surface can be partially exposed at the plastic / air interface. Figure 38 shows an example of a functionalized surface comprising an ABS plastic substrate coated with functional particles via a plastic solvent. Optionally, the powder can be electrostatically applied to the plastic surface.

[0126] Example 17: A functional powder is prepared via the method described in Examples 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15. The plastic is heated and temporarily melted. The functional powder is then deposited and the plastic is allowed to solidify while the powder is applied to and / or into the product. As illustrated in Figures 9(b) and 9(c), the resulting bulk and / or surface composite consists of the functional powder applied to the plastic surface and / or within the bulk. The functional powder surface may be partially exposed at the plastic / air interface. Optionally, the powder may be electrostatically applied to the plastic surface.

[0127] Example 18: A functional powder is prepared via the method described in Examples 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15. A binder medium is applied to the surface of the product. The binder may be applied by spraying, rolling, coating, brushing, stamping, or any other deposition technique. The functional powder is deposited in the binder medium, leaving the product coated with functional powder particles partially exposed at the surface / air interface, as illustrated in Figure 9(a). Optionally, paint may be used as the binder medium.

[0128] Example 19: A functional powder is prepared via the method described in Examples 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15. An acrylic paint or another polymeric paint (or coating) is applied to the surface of the product. The functional powder is then applied to the surface by temporarily liquefying the paint with a chemical solvent. Examples of plastic solvents include, but are not limited to, dichloromethane, benzene, toluene, hexane, hexanes, petroleum ether, acetone, acetaldehyde, methanol, analine, carbon tetrachloride, cyclohexane, diethyl ether, xylene, methyl ethyl ketone, methyl acetate, trichloroethylene, and methyl methacrylate monomer. The solvent and functional powder may be applied to the surface in any order or simultaneously, after which the solvent is allowed to evaporate and the paint is allowed to solidify. The resulting composition consists of the functional powder applied to the surface. As illustrated in Figure 9(a), the surface of the functional powder may be partially exposed at the paint / air interface. Optionally, the powder may be electrostatically applied to the surface of the paint.

[0129] Example 20: A functional powder is prepared via the method described in Example 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15. The functional powder is suspended in a metal adhesion paint via stirring. The paint is applied to a working surface of a set of medical devices or equipment in a thin layer. The paint is allowed to dry, leaving the metal surface coated with functional powder particles partially exposed at the paint / air interface, as illustrated in Figure 9(a).

[0130] Example 21: A functional powder is prepared via the method described in Examples 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15. The functional powder is temporarily fixed to the inner surface of a mold for casting a product such as a medical device or instrument. The mold is filled with liquid plastic, and the plastic is then allowed to solidify. The functional powder particles are embedded in the plastic surface, where the nanostructures may be partially exposed to the atmosphere.

[0131] Example 22: A functional powder is prepared via the method described in Examples 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15. The powder is suspended in a metal adhesion paint via stirring. The paint is applied to the exterior surface of the surface vessel in a thin layer. The paint is allowed to dry, leaving the metal surface coated with functional powder particles partially exposed at the paint / air interface. Due to the presence of nano- and micro-structures on the surface of the surface vessel, the vessel can have anti-fouling and hydrophobic properties, which act to prevent aquatic organisms from adhering to the surface of the surface vessel and to reduce drag.

[0132] Example 23: A functional powder is prepared via the method described in Examples 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15. Using conventional powder coating techniques, thermosetting polymer particles are applied to the surface via electrostatic charge. The functional powder is then applied to the surface. Optionally, the functional powder may be applied to the surface via electrostatic charge. The product is then cured with heat to attach the functional particles to the product surface. The thermosetting polymer acts as a binder between the substrate and the functional particles. The surface of the functional powder may be partially exposed at the paint / air interface.

[0133] Example 24: A functional powder is prepared via the method described in Examples 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15. At least a portion of a metal article is temporarily melted via heat. The functional powder is then applied to the molten metal. The metal is allowed to solidify while the functional particles are attached to the metal article.

[0134] Example 25: A functional powder is prepared via the method described in Examples 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15. A sterile, predetermined amount of functional powder is added to a sterile reactor, or a sterile functional powder is applied to the inside surface of a sterile reactor. Cells such as E. coli or C. albicans in an aqueous solution (e.g., 500 μL) such as nutrient broth (or another solution such as NaCl (e.g., 0.14 M)) are added to the reactor containing the functional particles. The reactor is then closed, and the entire system is stirred / vortexed (e.g., for 30 seconds). Optionally, after stirring / vortexing, the reactor is allowed to stand (e.g., up to 1 hour) to allow the contents to settle, or the reactor is centrifuged to aid in content separation. Figure 30 shows an example of an illustrative depiction of this method. The functionalized particles can increase the rate of cell lysis and allow for the extraction of intracellular components, including but not limited to DNA, RNA, macromolecules, proteins, organelles, and metabolites. These intracellular components may then be utilized in downstream analyses, experimental protocols, or tests. Optionally, the functionalized particles may also be chemically functionalized to aid in lysis and / or intracellular component extraction.

[0135] Cell lysis with non-functionalized particles (e.g., bead beating) may require longer stirring / vortexing durations compared to functionalized particles because cell lysis relies on ballistic interactions between the non-functionalized particles and the cells, which may lead to elevated temperatures in the reactor and temperature-sensitive contents. On the other hand, cell lysis with functionalized particles also involves interactions with particle surface structures, which may aid the lysis process. Functionalized particles can lyse cells with less mechanical energy, thus resulting in less heat load or heat transfer to the vessel and its contents (and therefore less damage to intracellular components).

[0136] In one example, functionalized particles were prepared via the method described in Example 7, with an etching duration of 60 minutes, and residual Ag was removed. These functionalized particles were sterilized and added to a sterile reactor with E. coli in 500 μL of LB broth (OD600 1.1). The reactor was vortexed for 30 seconds and left at 37°C for 1 hour. Compared to using non-functionalized Si particles, the functionalized Si particles showed a 533% increase in lysed E. coli, as seen in FIG. 31. The non-functionalized Si particles lysed 9% of the cells via ballistic interactions. Meanwhile, the functionalized Si particles lysed 57% of the cells via an additional mechanism via interactions between the functionalized surface structures and the cell membrane. Optionally, other types of cells may be lysed in this manner. The volume of the solution, duration, and intensity of agitation may be varied depending on the application.

[0137] Example 26: The surface of the product is prepared via the method described in Examples 16, 17, 18, 19, 23, or 24. The exposed structure of the functionalized particles may have antimicrobial properties that physically disrupt colonization or kill microorganisms. Figure 29 shows a fluorescence microscopy image of an exemplary Z-stack composition of the surface prepared on an ABS plastic substrate via the method described in Example 16, where the functionalized particles were prepared via the method described in Example 7, the etching duration was 60 minutes, and the residual Ag was removed. The cell viability was measured using the BacLight Live / Dead Fluorescence Kit (L7012 made of Propidium Iodide and SYTO9 components) according to the manufacturer's recommended method. Averaged across the micrographs of the three functionalized surfaces, 89±6% of E. coli (adjusted to OD600 0.3) was killed after 1 hour of contact at optimal growth conditions (37°C). The results show that the bacteria are killed by physical interactions between the functionalized particle surface structure and the bacterial membrane, which does not rely on resistance to promote chemical antibacterial properties. Optionally, the functionalized particles can be further chemically functionalized to disrupt colonization or kill microorganisms. Optionally, the particles can be further functionalized with functionalizing compounds to change or increase hydrophobicity or hydrophilicity.

[0138] Example 27: Functionalized powder particles are prepared via the methods described in Examples 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15. The functionalized particles have a greater surface roughness over many length scales than their non-functionalized counterparts and may be used to abrade or polish other materials. For example, the abrasive functionalized particles may be used as an abrasive in blasting, abrasive tumbling.

[0139] Example 28: A composite product is prepared via the methods described in Examples 16, 17, 18, 19, 23, or 24. The functionalized particles have a greater surface roughness over many length scales than their non-functionalized counterparts and may be used to abrade or polish other materials. The functionalized particles and their applications are selected for their abrasive or polishing properties. The product may be used to abrade or polish other materials or products.

[0140] Example 29: Antireflective surfaces are prepared via the methods described in Examples 16, 17, 18, 19, 23, or 24. For example, FIG. 37 shows specular reflectance (190-900 nm wavelength) data from several surfaces at an incidence angle of 45°. Samples include ABS plastic substrates coated via the methods described in Example 16 with functionalized powder particles prepared via the methods described in Example 2 (Sample E), Example 11 (Sample D), and Example 13 (Sample C), and non-functionalized Si powder particles (Sample F). A bare ABS substrate (Sample B) and a polished Si wafer (Sample A) are shown as references. The average reflectance of sample E shown in Figure 37 is 0.026% for light between 190-900 nm, 0.029% for light between 190-380 nm, 0.021% for light between 380-740 nm, and 0.033% for light between 740-900 nm. The average reflectance of sample D is 0.035% for light between 190-900 nm, 0.046% for light between 190-380 nm, 0.024% for light between 380-740 nm, and 0.045% for light between 740-900 nm. The average reflectance of sample C is 0.077% for light between 190-900 nm, 0.13% for light between 190-380 nm, 0.055% for light between 380-740 nm, and 0.062% for light between 740-900 nm. The average reflectance of Sample F is 0.085% for light between 380-900 nm, 0.081% between 380-740 nm, and 0.095% between 740-900 nm. The reduction in reflectance between surfaces containing non-functionalized Si powder particles (Sample F) and surfaces containing functionalized particles (Samples C, D, and E) is significant over a wide range of wavelengths. For example, the average reflectance of Sample F between 380-740 nm is approximately four times that of Sample E. Furthermore, these functionalized particle-surface composites, due to their nanoscale and microscale morphology, prevent reflection over a wide range of angles.

[0141] Example 30: Antifouling or hydrophobic surfaces are prepared via the methods described in Examples 16, 17, 18, 19, 23, or 24. The micro- and nano-scale texture formed on the surface by functional particles changes the surface energy of the product. For example, FIG. 27 shows contact angle measurements of ABS plastic substrates functionalized via attached functional Si particles, functional SiO particles, and non-functional Si particles. A polished Si wafer and a bare ABS substrate are shown for comparison. A functional ABS plastic substrate was prepared via the method described in Example 16 and spread 100% on the test surface. The Si wafer and particles on Samples 1, 2, 3, 4, and 5 contain natural oxides. Samples 1, 2, 3, and 4 contain functional particles and have contact angles greater than 90°, indicating that these surfaces are hydrophobic. The bare ABS substrate, polished Si wafer, and Example 5 have contact angles less than 90°, indicating that these surfaces are hydrophilic. The modification to the surface energy can be seen by comparing the contact angles of polished Si wafers, Sample 1, Sample 2, Sample 3, and Sample 5, all of the same Si chemical composition. The microscale texture formed by Sample 5 on the non-functionalized Si particle surface shows an increase in the contact angle compared to the Si wafer. Samples 1, 2, and 3 show an increase in the contact angle due to their functionalized surface structure. The combination of low surface energy, hydrophobicity, and antimicrobial properties of some functionalized particles may result in antifouling activity. Optionally, chemical functionalization may increase the hydrophobicity or antifouling properties of the coating.

[0142] Example 31: A surface is prepared via the methods described in Examples 16, 17, 18, 19, 23, or 24. A conductive material is then applied to the functionalized particles exposed via conventional techniques to form a conductive surface with a surface area that is at least twice that of the contact. The micro- and nanoscale structures will increase the capacitance per contact area. The micro- and nanoscale features may increase the discharge from the surface. Figure 5(d) shows an example of a cross-sectional SEM image of a Pt-coated prismatic structure.

[0143] Example 32: The band structure of functional powders is altered by preparing functional powder particles via the methods described in Examples 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15. Structural functionalization may result in anisotropic stretching of the crystal lattice, which may result in a change in the band structure of the particles. The anisotropic lattice modification may be localized to the portion of the particle that is structurally functionalized (i.e., radially dependent) or may be altered throughout the particle (i.e., radially independent). In this manner, the band structure may be altered without changing the chemical composition of the particle. For example, FIG. 25 shows X-ray diffraction data from non-functionalized Si particles and functionalized powder particles prepared via the method described in Example 7 with 90 minutes of etching. A shift in peak position can be seen for the Si(111) and Si(311) peaks of the functionalized powder, which indicates that <111> 0.194% lattice elongation along the direction, and <311> direction, whereas the positions of the Si(220), Si(400) and Si(331) peaks remain unchanged. The X-ray data suggest that the crystalline unit cell is anisotropic and deformed for the entire particle (average diameter 45 μm) by the structural functionalization at the surface (thickness 1.5 μm). If the lattice modification was radiation dependent, it would have resulted in a multicomponent Bragg peak (due to X-ray scattering contributions from the particle core and the functionalized regions), which is not present in the X-ray data. The structural functionalization of a relatively small portion of the particle without changing the chemical composition altered the crystal lattice of the entire particle.

[0144] Example 33: Fade-resistant opaque pigments are prepared via the methods described in Examples 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15. Some pigments rely on chromophores to fade due to high-energy radiation (such as UV light) exposure that damages the color-carrying molecules. The optical properties of functionalized particles depend on both bulk material properties and the particle surface structure. For example, Samples A, C, E, and F in FIG. 37 have the same bulk composition and crystal structure, but different surface morphologies. Different surface structures have a significant effect on the light reflectance and surface appearance. The matte black appearance of Sample E is due to the structurally light-absorbing particle functional structure. Structurally functionalized particles used as pigments may be more fade-resistant because their color is not solely dependent on molecular structure.

[0145] While preferred embodiments of the present invention have been shown and described herein, it will be apparent to those skilled in the art that such embodiments are provided by way of example only. Numerous modifications, changes, and substitutions will occur to those skilled in the art without departing from the invention. It is understood that various alternatives to the embodiments of the invention described herein may be utilized in practicing the invention. It is intended that the following claims define the scope of the invention and that methods and structures within the scope of these claims and their equivalents are covered thereby.

Claims

1. 1. A method for disrupting a cell membrane in a cell, the method comprising: (a) providing a container containing a chamber comprising one or more surface-etched powder particles, each of the one or more surface-etched powder particles independently comprising a crystalline, polycrystalline, semi-crystalline, or amorphous semiconductor or insulator powder particle, the surfaces of the powder particles being etched such that each of the surface-etched powder particles comprises one or more structures selected from pores, pits, nanowires, cones, pillars, corals, cords, walls, fins, ridges, pyramids, and inverted pyramids, each of the surface-etched powder particles having a diameter of 0.01 to 1,000 microns; and (b) flowing a composition comprising the cells through a vessel containing the chamber, wherein the one or more surface-etched powder particles physically or chemically interact with the cells, thereby rupturing the cell membranes. A method comprising:

2. 2. The method of claim 1, wherein the crystalline, polycrystalline, semi-crystalline, or amorphous surface-etched powder particles are crystalline, polycrystalline, semi-crystalline, or amorphous surface-etched powder particles of an element or compound selected from Group IVA elements, Group IV-VI compounds, Group II-IVB compounds, Group I-VII compounds, Group II-VI compounds, Group III-V compounds, Group IV-IV compounds, transition metal oxides, and compounds containing three or more elements.

3. The method of claim 1 or 2, wherein the surface-etched powder particles include one or more grains.

4. 4. The method of claim 1, wherein the surface-etched powder particles consist of single crystal grains.

5. 5. The method of claim 1, wherein the surface-etched powder particles comprise a heterogeneous mixture of different size particles configured to provide increased packing density.

6. 6. The method of claim 1, wherein the surface-etched powder particles comprise two or more structures selected from pores, pits, nanowires, cones, pillars, corals, fins, ridges, pyramids, and inverted pyramids.

7. The method of claim 1 , wherein the one or more structures are sub-millimeter structures.

8. The method of claim 1 , wherein the one or more structures are selected from microstructures and nanostructures.

9. 9. The method of claim 1, wherein the average diameter of the smallest 30% of the surface-etched powder particles is 200% smaller than the average diameter of the largest 10% of the surface-etched powder particles.

10. 10. The method of claim 1, further comprising a film separating the surface-etched powder particles from the atmosphere.

11. 11. The method of any one of claims 1 to 10, wherein the surface of the powder particles is antireflective, reflective, adsorptive, conductive, insulating, antistatic, luminescent, antibacterial, non-wetting, hydrophobic, hydrophilic, antifouling, abrasive, anti-adhesive, anti-slip, or a combination thereof.

12. 12. The method of any one of claims 1 to 11, wherein the surface-etched powder particles lyse one or more cells, and the surface-etched powder particles physically or chemically interact with the cells.

13. A method according to any one of claims 1 to 12, further comprising the step of transferring or replicating the surface structure of the article using the surface-etched powder particles as a template or mold by contacting the surface structure of the article with at least one of the surface-etched powder particles.

14. 1. A method for lysing a cell, the method comprising: (a) providing a container containing a chamber containing one or more surface-etched powder particles, wherein the surfaces of the powder particles are etched such that each of the surface-etched powder particles comprises one or more sub-millimeter structures selected from the group consisting of pores, pits, nanowires, cones, pillars, corals, cords, walls, fins, ridges, pyramids, and inverted pyramids, and wherein the diameter of the surface-etched powder particles is between 0.01 and 1,000 microns; and (b) flowing a composition comprising the cells through a vessel containing the chamber, such that the one or more surface-etched powder particles contact the cells, thereby lysing the cells; A method comprising:

15. 15. The method of any one of claims 1 to 14, wherein the surface-etched powder particles do not embed or adhere to the walls or surfaces of the container, respectively.

16. The method of claim 15 , wherein each of the surface-etched powder particles flows through the container.

Citation Information

Patent Citations

  • Antimicrobial filter and its manufacture

    JP1999290626A

  • Method and apparatus for evaluating removal of microorganism

    JP2004159636A

  • Solid-phase cell lysis and capture platform

    JP2006525807A

  • A synthetic antiseptic surface containing an array of nanospikes

    JP2017503554A

  • Gum compositions

    US20110268779A1